Polarizing film with adhesive layer and liquid crystal panel

By using a polarizing film with an adhesive layer in a liquid crystal display device, the transmittance loss and surface resistivity of the conductive layer are controlled, solving the problems of poor display and decreased visual recognizability caused by static electricity, and achieving display stability and clarity in a highly anti-static environment.

CN113748374BActive Publication Date: 2025-02-18NITTO DENKO CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202080032191.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-13
Filing Date
2020-06-23
Publication Date
2025-02-18
Estimated Expiration
2040-06-23

AI Technical Summary

Technical Problem

In liquid crystal display devices, especially in environments with abundant electronic devices such as vehicles, static electricity can easily cause display problems, while the low surface resistivity of the conductive layer can lead to a decrease in visual legibility.

Method used

A polarizing film with an adhesive layer is used, comprising a polarizing film, a conductive layer, and an adhesive layer. The total light transmittance loss of the conductive layer is controlled below 0.9%, and the surface resistivity is below 1.0×10⁶Ω/□, ensuring antistatic properties and visual recognizability.

Benefits of technology

It effectively prevents display defects caused by static electricity in LCD devices while maintaining good visual legibility, making it suitable for high anti-static environments such as automotive displays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113748374B_ABST
    Figure CN113748374B_ABST
Patent Text Reader

Abstract

The present invention provides a polarizing film with an adhesive layer that can prevent poor display caused by charging of a liquid crystal display device and suppress the deterioration of the visual recognition of the liquid crystal display device. The polarizing film with an adhesive layer of the present invention comprises a polarizing film and an adhesive layer. The polarizing film with an adhesive layer further comprises a conductive layer, and the loss of total light transmittance caused by the conductive layer is 0.9% or less. The surface resistivity of the conductive layer is 1.0×10 6 Ω / □ or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polarizing film with an adhesive layer and a liquid crystal panel. Background Art

[0002] The liquid crystal display device includes, for example, a liquid crystal panel having a polarizing film disposed on a visible side of a liquid crystal cell and an illumination system for irradiating light to the liquid crystal panel. The liquid crystal display device displays an image by applying voltage to the liquid crystal cell and adjusting the alignment of liquid crystal molecules contained in the liquid crystal cell.

[0003] For a liquid crystal display device, static electricity is generated during manufacturing, for example, when a polarizing film is attached to a liquid crystal cell via an adhesive layer, or during use, for example, when a user touches the liquid crystal display device. The liquid crystal display device may be charged due to the static electricity. If the liquid crystal display device is charged, the orientation of the liquid crystal molecules contained in the liquid crystal cell is disordered, and poor display may occur. In order to prevent poor display caused by charging of the liquid crystal display device, it is known that an ITO (indium tin oxide) layer is arranged on the surface of the liquid crystal cell on the side of the polarizing film, for example.

[0004] Patent Documents 1 and 2 disclose a laminated structure including a polarizing film and a conductive layer containing a conductive polymer.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2016-39132

[0008] Patent Document 2: Japanese Patent Application No. 2015-509615 Summary of the invention

[0009] Problems to be solved by the invention

[0010] According to the research of the inventors, it is known that when a liquid crystal display device is used in an environment where static electricity is particularly likely to be generated, such as the interior of a vehicle where other electronic devices are present around, in order to fully prevent display defects caused by charging of the liquid crystal display device, the surface resistivity of the conductive layer needs to be adjusted to a lower value. However, if the surface resistivity of the conductive layer is adjusted to a lower value, the transmittance of the conductive layer decreases, and the visual recognition of the liquid crystal display device deteriorates.

[0011] Therefore, the object of the present invention is to provide a polarizing film with an adhesive layer that can prevent display defects caused by charging of the liquid crystal display device and suppress the deterioration of the visual recognition of the liquid crystal display device even for a liquid crystal display device that requires high antistatic properties, such as a car-mounted display.

[0012] Solutions to the problem

[0013] The present invention provides a polarizing film with an adhesive layer, comprising a polarizing film and an adhesive layer.

[0014] The polarizing film with an adhesive layer further comprises a conductive layer.

[0015] The total light transmittance loss caused by the conductive layer is less than 0.9%.

[0016] The surface resistivity of the conductive layer is 1.0×10 6 Ω / □ or less.

[0017] Effects of the Invention

[0018] According to the present invention, it is possible to provide a polarizing film with a pressure-sensitive adhesive layer that can prevent display defects caused by charging of a liquid crystal display device and suppress deterioration in visibility of the liquid crystal display device. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a cross-sectional view of a pressure-sensitive adhesive layer-attached polarizing film according to one embodiment of the present invention.

[0020] Figure 2 It is a cross-sectional view showing a modified example of the polarizing film with a pressure-sensitive adhesive layer.

[0021] Figure 3 This is a cross-sectional view showing an example of an antireflection film.

[0022] Figure 4 It is a cross-sectional view showing another example of the antireflection film.

[0023] Figure 5 This is a cross-sectional view showing another modified example of the polarizing film with an adhesive layer.

[0024] Figure 6 This is a cross-sectional view of a liquid crystal panel including the pressure-sensitive adhesive layer-attached polarizing film of the present invention.

[0025] Figure 7 This is a cross-sectional view of a liquid crystal panel according to another embodiment of the present invention.

[0026] Figure 8 This is a graph showing the relationship between the surface resistivity of the conductive layer of the pressure-sensitive adhesive layer-attached polarizing film of Examples 1 to 12 and Comparative Examples 1, 2, and 4 and the loss of total light transmittance caused by the conductive layer.

[0027] Fig. 9 The graph shows the reflected light from the pressure-sensitive adhesive layer-attached polarizing film of Examples 13 to 26 and Comparative Examples 5 and 6. * Value and b * A graph of the relationship of the values. DETAILED DESCRIPTION

[0028] In one embodiment of the present invention, the polarizing film, the conductive layer and the adhesive layer are stacked together in the above order.

[0029] In one embodiment of the present invention, the loss of total light transmittance caused by the conductive layer is 0.5% or less.

[0030] In one embodiment of the present invention, the loss of total light transmittance caused by the conductive layer is 0.4% or less.

[0031] In one embodiment of the present invention, the surface resistivity of the conductive layer is 5.0×10 5 Ω / □ or less.

[0032] In one embodiment of the present invention, the surface resistivity of the conductive layer is 1.0×10 4 Ω / □ or less.

[0033] In one embodiment of the present invention, the surface resistivity of the conductive layer is greater than 5.0×10 2 Ω / □.

[0034] In one embodiment of the present invention, at least one of the following (i) and (ii) is satisfied: (i) the total light transmittance loss caused by the conductive layer is 0.5% or less, and the surface resistivity of the conductive layer is 1.0×10 6 Ω / □ or less; and (ii) the total light transmittance loss caused by the conductive layer is less than 0.9%, and the surface resistivity of the conductive layer is 1.0×10 4 Ω / □ or less.

[0035] In one embodiment of the present invention, the adhesive layer comprises a conductive material.

[0036] In one embodiment of the present invention, the pressure-sensitive adhesive layer-attached polarizing film further includes an antireflection film, and the antireflection film, the polarizing film, and the pressure-sensitive adhesive layer are arranged in the above order in the lamination direction.

[0037] In one embodiment of the present invention, a polarizing film with an adhesive layer having an anti-reflection film generates reflected light with a light reflectance Y of less than 1.1% when light from a CIE standard light source D65 is incident from a surface opposite to the adhesive layer in a state in which the adhesive layer is stacked on the alkali-free glass in direct contact with the alkali-free glass.

[0038] In one embodiment of the present invention, the reflected light is * a * b * a in the color system * Value and b *The values ​​satisfy the following relations (1) and (2).

[0039] -10≤a * ≤10 (1)

[0040] -18≤b * ≤5 (2)

[0041] In one embodiment of the present invention, the antireflection film includes a first high refractive index layer, a first low refractive index layer, a second high refractive index layer, and a second low refractive index layer in this order in a lamination direction.

[0042] In one embodiment of the present invention, the optical film thickness of the first high refractive index layer is 20nm to 35nm, the optical film thickness of the first low refractive index layer is 38nm to 50nm, the optical film thickness of the second high refractive index layer is 230nm to 290nm, and the optical film thickness of the second low refractive index layer is 100nm to 128nm.

[0043] In addition, the present invention provides a liquid crystal panel having:

[0044] Polarizing film with adhesive layer, and

[0045] Liquid crystal unit,

[0046] No conductive layer was provided between the polarizing film with an adhesive layer and the liquid crystal cell.

[0047] Hereinafter, the present invention will be described in detail, but the following description is not intended to limit the present invention to specific embodiments.

[0048] (Embodiments of Polarizing Film with Adhesive Layer)

[0049] like Figure 1 As shown, the polarizing film 10 with an adhesive layer of the present embodiment includes a polarizing film 1, a conductive layer 2, and an adhesive layer 3. The polarizing film 1, the conductive layer 2, and the adhesive layer 3 are stacked together, for example, in the above order, and the conductive layer 2 is in contact with the polarizing film 1 and the adhesive layer 3, respectively. In the case where the conductive layer 2 is arranged between the polarizing film 1 and the adhesive layer 3, there is a tendency that the deterioration of the conductive layer 2 is suppressed. However, the conductive layer 2 may be arranged at a position other than between the polarizing film 1 and the adhesive layer 3, for example, the polarizing film 1 may be arranged between the conductive layer 2 and the adhesive layer 3. The surface of the adhesive layer 3 is exposed, for example, outside the polarizing film 10 with an adhesive layer.

[0050] In the polarizing film 10 with an adhesive layer, the loss A of the total light transmittance caused by the conductive layer 2 is less than 0.9%. According to the research of the inventors, when the loss A is suppressed to this extent, the deterioration of the visual recognition of the liquid crystal display device can be fully suppressed. The loss A can be specified by the following method. First, the total light transmittance T1 of the polarizing film 1 and the total light transmittance T2 of the laminate L including the polarizing film 1 and the conductive layer 2 are measured. In this specification, "total light transmittance" refers to the transmittance of light in the wavelength range of 380nm to 700nm. The total light transmittance can be measured based on the provisions of JIS K7361-1:1997. The total light transmittance is measured using a D65 light source. The total light transmittance T2 of the laminate L is the value when the light is from the side of the polarizing film 1. The difference (T1-T2) between the total light transmittance T1 and the total light transmittance T2 can be specified as the loss A.

[0051] When measuring the total light transmittance T1 and T2, a layer (such as a hard coating layer) that does not affect the value of the loss A may be arranged on the surface of the polarizing film 1. For example, the loss A can be specified as the difference (T3-T4) between the total light transmittance T3 of the laminate L1 including the hard coating layer H and the polarizing film 1 and the total light transmittance T4 of the laminate L2 including the hard coating layer H, the polarizing film 1, and the conductive layer 2. In the laminate L2, the hard coating layer H, the polarizing film 1, and the conductive layer 2 are laminated together in the above order. The total light transmittance T3 of the laminate L1 and the total light transmittance T4 of the laminate L2 are both values ​​when light is incident from the hard coating layer H side.

[0052] The above loss A is preferably 0.8% or less, more preferably 0.6% or less, further preferably 0.5% or less, particularly preferably 0.4% or less, and particularly preferably less than 0.2%. The lower limit of the loss A is not particularly limited, and is, for example, 0.01%.

[0053] In the polarizing film 10 with an adhesive layer, the surface resistivity of the conductive layer 2 is 1.0×10 6Ω / □ or less. The conductive layer 2 having a surface resistivity as low as this can prevent poor display caused by charging of a liquid crystal display device having a polarizing film 10 with an adhesive layer even in an environment where static electricity is easily generated. The surface resistivity of the conductive layer 2 can be determined by the following method. First, a laminate in which the surface of the conductive layer 2 is exposed to the outside is prepared. Examples of such laminates include a laminate L comprising a polarizing film 1 and a conductive layer 2, and a laminate L2 comprising a hard coating layer H, a polarizing film 1, and a conductive layer 2. Next, the surface resistivity of the surface of the conductive layer 2 in the prepared laminate is measured. The surface resistivity can be measured according to the method specified in JIS K7194:1994 or JIS K6911:1995. As an example, when the surface resistivity of the conductive layer 2 is less than 1.0×10 5 Ω / □, the surface resistivity of the conductive layer 2 can be measured using Loresta-GP MCP-T600 (manufactured by Mitsubishi Chemical Analytech Co., Ltd.) in accordance with the method specified in JIS K7194:1994. 5 When the surface resistivity of the conductive layer 2 is 0.0447 W / m or more, the surface resistivity of the conductive layer 2 can be measured using Hiresta-UP MCP-HT450 (manufactured by Mitsubishi Chemical Analytech Co., Ltd.) according to the method specified in JIS K6911: 1995. The measured value obtained by the above measurement can be regarded as the surface resistivity of the conductive layer 2 in the pressure-sensitive adhesive layer-attached polarizing film 10.

[0054] The surface resistivity of the conductive layer 2 is preferably 5.0×10 5 Ω / □ or less, more preferably 1.0×10 5 Ω / □ or less, more preferably 1.0×10 4 Ω / □ or less, particularly preferably 1.0×10 3 Ω / □ or less. The lower limit of the surface resistivity of the conductive layer 2 is not particularly limited, but is, for example, 1.0×10 2 Ω / □. When the polarizing film 10 with an adhesive layer is used in a liquid crystal display device having a touch sensor or a touch panel, the surface resistivity of the conductive layer 2 may be greater than 5.0×10 2 Ω / □.

[0055] In the polarizing film 10 with an adhesive layer, when the loss A is greater than 0.5%, the surface resistivity of the conductive layer 2 can be particularly low. As an example, in the polarizing film 10 with an adhesive layer, at least one of the following (i) and (ii) is satisfied: (i) the loss A is less than 0.5% and the surface resistivity of the conductive layer 2 is 1.0×10 6 Ω / □ or less; and (ii) the above-mentioned loss A is less than 0.9%, and the surface resistivity of the conductive layer 2 is 1.0×10 4 Ω / □ or less.

[0056] [Polarizing film]

[0057] The polarizing film 1 is a laminate including a polarizer and a transparent protective film. The transparent protective film is arranged, for example, in contact with the main surface (surface with the largest area) of the layered polarizer. The polarizer can be arranged between two transparent protective films. As a polarizer, there is no particular limitation, and examples thereof include polarizers obtained by adsorbing dichroic substances such as iodine and dichroic dyes on hydrophilic polymer films such as polyvinyl alcohol films, partially formalized polyvinyl alcohol films, and partially saponified films of ethylene-vinyl acetate copolymers and uniaxially stretching them; polyene oriented films such as dehydrated products of polyvinyl alcohol and dehydrochlorinated products of polyvinyl chloride, etc. The polarizer is preferably formed of dichroic substances such as polyvinyl alcohol films and iodine.

[0058] The thickness of the polarizer is not particularly limited, and is, for example, 80 μm or less. The thickness of the polarizer may be 10 μm or less, preferably 1 to 7 μm. Such a thin polarizer has less uneven thickness and excellent visual recognition. The dimensional change of the thin polarizer is suppressed, and the durability is excellent. By using a thin polarizer, the polarizing film 1 can be thinned.

[0059] As the material of the transparent protective film, for example, a thermoplastic resin having excellent transparency, mechanical strength, thermal stability, moisture barrier property, isotropy, etc. can be used. Specific examples of such thermoplastic resins include cellulose resins such as cellulose triacetate, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. The material of the transparent protective film can be a thermosetting resin or an ultraviolet curing resin such as (meth)acrylic, urethane, acrylic urethane, epoxy, silicone, etc. In the case where the polarizing film 1 has two transparent protective films, the materials of the two transparent protective films can be the same or different. For example, a transparent protective film made of a thermoplastic resin can be bonded to one main surface of the polarizer using an adhesive, and a transparent protective film made of a thermosetting resin or an ultraviolet curing resin can be bonded to the other main surface of the polarizer. The transparent protective film may contain one or more optional additives.

[0060] The transparent protective film may have optical properties such as anti-glare properties and anti-reflection properties. The transparent protective film may be a film that functions as a phase difference film. In this specification, a phase difference film refers to a film having birefringence in the in-plane direction or the thickness direction. Films that function as phase difference films include, for example, films obtained by stretching a polymer film, films obtained by orienting and fixing a liquid crystal material, and the like.

[0061] The adhesive used to bond the polarizer to the transparent protective film is not particularly limited as long as it is optically transparent, and examples thereof include aqueous, solvent-based, hot melt-based, radical-curable, and cation-curable adhesives, with aqueous adhesives and radical-curable adhesives being preferred.

[0062] The thickness of the polarizing film 1 is, for example, 10 μm to 500 μm. The total light transmittance of the polarizing film 1 is not particularly limited, but is, for example, 30% to 50%.

[0063] When light from CIE standard light source D65 is incident on the polarizing film 1, the a value of the transmitted light in the Hunter Lab color system is preferably -6.0 to 0, more preferably -3.0 to -0.5, and particularly preferably -1.8 to -1.2. The b value of the above-mentioned transmitted light in the Hunter Lab color system is preferably 1.0 to 10, more preferably 1.5 to 5.0, and particularly preferably 2.2 to 4.0. The a value and b value of the transmitted light in the Hunter Lab color system can be specified by the following method. First, the transmittance of light from CIE standard light source D65 in the polarizing film 1 is measured using an integrating sphere of a spectrophotometer. For the obtained transmittance, a visibility correction (780 to 380 nm: 5 nm interval) is performed using the 2-degree field of view XYZ system specified in JIS Z8701:1999, thereby specifying the a value and b value of the transmitted light in the Hunter Lab color system.

[0064] [Conductive layer]

[0065] The conductive layer 2 has a surface resistivity of 1.0×10 6 Ω / □ or less and the above-mentioned loss A is adjusted to less than 0.9%, there is no special limitation. The conductive layer 2 is a layer containing a conductive material. The conductive material may also be a material other than ITO, such as a conductive polymer, a composite of a conductive polymer and a dopant, an ionic surfactant, conductive particles, an ionic compound, etc. From the perspective of transparency, total light transmittance, appearance, antistatic effect, and stability of the antistatic effect in a high temperature or humid environment, it is preferred that the conductive layer 2 contains a conductive polymer. In the case where the conductive layer 2 contains a conductive polymer as a conductive material, compared with the case where the conductive particles are contained, even if the thickness of the conductive layer 2 is adjusted to a large extent, it is not easy to generate fog. Therefore, even if the conductive layer 2 is arranged between the liquid crystal unit and the polarizer, the conductive layer 2 containing the conductive polymer is not easy to eliminate polarized light and is not easy to reduce the contrast of the image displayed by the liquid crystal display device. In the case where the conductive layer 2 contains a conductive polymer as a conductive material, there is a tendency for the refractive index of the conductive layer 2 to be lower than that of the conductive particles. Therefore, the conductive layer 2 containing a conductive polymer is suitable for reducing the reflectivity of light of the liquid crystal panel.

[0066] As the conductive polymer, for example, polythiophene, polyaniline, polypyrrole, polyquinoxaline, polyacetylene, polyphenylene vinylene, polynaphthalene and their derivatives can be cited. The conductive material can contain one or more of these conductive polymers. As the conductive polymer, polythiophene, polyaniline and their derivatives are preferred, and polythiophene derivatives are particularly preferred. Polythiophene, polyaniline and their derivatives function, for example, as water-soluble or water-dispersible conductive polymers. In the case where the conductive polymer is water-soluble or water-dispersible, the conductive layer 2 can be prepared using an aqueous solution or aqueous dispersion of the conductive polymer. In this case, the preparation of the conductive layer 2 does not require the use of a non-aqueous organic solvent, and therefore, the degradation of the polarizing film 1 and the like caused by the organic solvent can be suppressed.

[0067] The conductive polymer may have a hydrophilic functional group. Examples of the hydrophilic functional group include a sulfonic group, an amino group, an amide group, an imino group, a hydroxyl group, a thiol group, a hydrazine group, a carboxyl group, a sulfate group, a phosphate group, and salts thereof (e.g., a quaternary ammonium salt group). When the conductive polymer has a hydrophilic functional group, there is a tendency that the conductive polymer is easily soluble in water, or that the conductive polymer in a microparticle form is easily dispersed in water.

[0068] From the viewpoint of conductivity and chemical stability, the conductive polymer is preferably poly(3,4-disubstituted thiophene). Examples of the poly(3,4-disubstituted thiophene) include poly(3,4-alkylenedioxythiophene) and poly(3,4-dialkoxythiophene), and poly(3,4-alkylenedioxythiophene) is preferred. The poly(3,4-alkylenedioxythiophene) has a structural unit represented by the following formula (I), for example.

[0069] [Chemical formula 1]

[0070]

[0071] In formula (I), R 1 For example, it is an alkylene group having 1 to 4 carbon atoms. The alkylene group may be linear or branched. Examples of the alkylene group include methylene, 1,2-ethylene, 1,3-propylene, 1,4-butylene, 1-methyl-1,2-ethylene, 1-ethyl-1,2-ethylene, 1-methyl-1,3-propylene, and 2-methyl-1,3-propylene, preferably methylene, 1,2-ethylene, and 1,3-propylene, and more preferably 1,2-ethylene. The conductive polymer is preferably poly(3,4-methylenedioxythiophene) (PEDOT).

[0072] As dopants, for example, polyanions can be cited. In the case where the conductive polymer is polythiophene (or its derivatives), the polyanion can form an ion pair with polythiophene (or its derivatives) to stably disperse the polythiophene (or its derivatives) in water. As polyanions, there are no special restrictions, and examples include: carboxylic acid polymers such as polyacrylic acid, polymaleic acid, and polymethacrylic acid; sulfonic acid polymers such as polystyrene sulfonic acid, polyvinyl sulfonic acid, and polyisoprene sulfonic acid. The polyanion can also be a copolymer of vinyl carboxylic acid or vinyl sulfonic acid and other monomers. As other monomers, for example: (meth) acrylate compounds; aromatic vinyl compounds such as styrene and vinyl naphthalene. The polyanion is particularly preferably polystyrene sulfonic acid (PSS). As a composite of a conductive polymer and a dopant, for example: a composite of poly (3,4-methylenedioxythiophene) and polystyrene sulfonic acid (PEDOT / PSS) can be cited.

[0073] Examples of the ionic surfactant include quaternary ammonium salt type, Cationic surfactants such as salt type and sulfonium salt type; anionic surfactants such as carboxylic acid type, sulfonate type, sulfate type, phosphate type, phosphite type; sulfobetaine type, alkyl betaine type, alkyl imidazole type Zwitterionic surfactants such as betaine type; nonionic surfactants such as polyol derivatives, β-cyclodextrin inclusion complexes, sorbitan fatty acid monoesters, sorbitan fatty acid diesters, polyoxyalkylene derivatives, and amine oxides.

[0074] As conductive particles, for example, metal oxide particles such as tin oxide, antimony oxide, indium oxide, and zinc oxide can be cited, preferably tin oxide particles. As materials for tin oxide particles, for example, tin oxide, antimony-doped tin oxide, indium-doped tin oxide, aluminum-doped tin oxide, tungsten-doped tin oxide, titanium oxide-cerium oxide-tin oxide complex, titanium oxide-tin oxide complex, etc. can be cited. The average particle size of the conductive particles is, for example, 1 to 100 nm, preferably 2 to 50 nm. The average particle size of the conductive particles refers to the particle size (d50) equivalent to 50% of the volume accumulation in the particle size distribution measured, for example, by a laser diffraction particle size analyzer.

[0075] As ionic compounds, for example, alkali metal salts and / or organic cation-anion salts can be mentioned. As alkali metal salts, for example, organic salts and inorganic salts of alkali metals can be mentioned. In this specification, organic cation-anion salts refer to organic salts containing organic cations. The anions contained in the organic cation-anion salts can be organic anions or inorganic anions. Organic cation-anion salts are sometimes referred to as ionic liquids or ionic solids.

[0076] Examples of the alkali metal ion contained in the alkali metal salt include lithium ion, sodium ion and potassium ion, and lithium ion is preferred.

[0077] Examples of anions contained in the organic salt of an alkali metal include CH3COO - CF3COO - 、CH3SO3 - CF3SO3 - 、(CF3SO2)3C - 、C4F9SO3 - 、C3F7COO - 、(CF3SO2)(CF3CO)N - , - O3S(CF2)3SO3 - 、(CN)2N - and anions represented by the following general formulae (a) to (d).

[0078] (a)(C n F 2n+1 SO2)2N - (where n is an integer from 1 to 10)

[0079] (b)CF2(C m F 2m SO2)2N - (wherein m is an integer from 1 to 10)

[0080] (c) - O3S(CF2) l SO3 - (wherein l is an integer from 1 to 10)

[0081] (d)(C p F 2p+1 SO2)N - (C q F 2q+1 SO2) (wherein p and q are independently integers of 1 to 10)

[0082] The anion contained in the organic salt of the alkali metal preferably contains a fluorine atom. The anion containing a fluorine atom allows the organic salt of the alkali metal to function as an ionic compound having excellent ion dissociation properties.

[0083] Examples of anions contained in the inorganic salt of an alkali metal include Cl - Br - ,I - 、AlCl4 - 、Al2Cl7 - 、BF4 - PF6- 、ClO4 - 、NO3 - 、AsF6 - 、SbF6 - 、NbF6 - 、TaF6 - 、(FSO2)2N - 、CO3 2- wait.

[0084] As the anion contained in the alkali metal salt, (CF3SO2)2N - 、(C2F5SO2)2N - The (perfluoroalkylsulfonyl)imide represented by the above general formula (1) is particularly preferably (CF3SO2)2N - Represents bis(trifluoromethanesulfonyl)imide.

[0085] Examples of the organic salt of the alkali metal include sodium acetate, sodium alginate, sodium lignin sulfonate, sodium toluene sulfonate, LiCF3SO3, Li(CF3SO2)2N, Li(C2F5SO2)2N, Li(C4F9SO2)2N, Li(CF3SO2)3C, KO3S(CF2)3SO3K, LiO3S(CF2)3SO3K, etc., preferably LiCF3SO3, Li(CF3SO2)2N, Li(C2F5SO2)2N, Li(C4F9SO2)2N, Li(CF3SO2)3C, more preferably Li(CF3SO2)2N, Li(C2F5SO2)2N, Li(C4F9SO2)2N. The organic salt of the alkali metal is preferably a fluorine-containing imide lithium salt, and particularly preferably a (perfluoroalkylsulfonyl)imide lithium salt.

[0086] Examples of inorganic salts of alkali metals include lithium perchlorate and lithium iodide.

[0087] Examples of the organic cation contained in the organic cation-anion salt include pyridine Cation, piperidine Cation, pyrrolidine Cation, cation having a pyrroline skeleton, cation having a pyrrole skeleton, imidazole Cation, Tetrahydropyrimidine Cation, dihydropyrimidine Cation, pyrazole Cationic, pyrazoline Cations, tetraalkylammonium cations, trialkylsulfonium cations, tetraalkyl Cations, etc.

[0088] Examples of anions contained in the organic cation-anion salt include Cl- Br - ,I - 、AlCl4 - 、Al2Cl7 - 、BF4 - PF6 - 、ClO4 - 、NO3 - 、CH3COO - CF3COO - 、CH3SO3 - CF3SO3 - 、(CF3SO2)3C - 、AsF6 - 、SbF6 - 、NbF6 - 、TaF6 - 、(CN)2N - 、C4F9SO3 - 、C3F7COO - 、(CF3SO2)(CF3CO)N - 、(FSO2)2N - , - O3S(CF2)3SO3 - and anions represented by the above general formulae (a) to (d). The anions contained in the organic cation-anion salt preferably contain fluorine atoms. The anions containing fluorine atoms allow the organic cation-anion salt to function as an ionic compound having excellent ion dissociation properties.

[0089] The ionic compound is not limited to the above-mentioned alkali metal salts and organic cation-anion salts, and can also include inorganic salts such as ammonium chloride, aluminum chloride, cupric chloride, ferrous chloride, ferric chloride, and ammonium sulfate. The conductive material may contain one or more of the above-mentioned ionic compounds.

[0090] Conductive materials are not limited to the above materials, and examples thereof include carbon materials such as acetylene black, Ketjen black, natural graphite, and artificial graphite; titanium black; homopolymers of monomers having cationic conductive groups such as quaternary ammonium salts, zwitterionic conductive groups such as betaine compounds, anionic conductive groups such as sulfonates, or non-ionic conductive groups such as glycerol, or copolymers of the monomers with other monomers (for example, polymers having ionic conductivity such as polymers having structural units derived from acrylates or methacrylates having quaternary ammonium salt groups); materials obtained by alloying hydrophilic polymers such as copolymers of ethylene and methacrylates with acrylic resins, etc. (permanent antistatic agents).

[0091] The conductive layer 2 may contain other materials such as adhesives in addition to the conductive material. The adhesive has a tendency to improve the film-forming property of the conductive material and to improve the adhesion and bonding (anchoring force) of the conductive layer 2 to the polarizing film 1. Examples of the adhesive include: Oxazoline polymers, polyurethane resins, polyester resins, acrylic resins, polyether resins, cellulose resins, polyvinyl alcohol resins, epoxy resins, polyvinyl pyrrolidone, polystyrene resins, polyethylene glycol, pentaerythritol, etc., preferably containing The conductive layer 2 may contain one or more of these binders. The content of the binder in the conductive layer 2 is, for example, 1 wt% to 90 wt%, preferably 10 wt% to 80 wt%.

[0092] The thickness of the conductive layer 2 is, for example, 5 nm to 180 nm, preferably 150 nm, more preferably 120 nm or less, further preferably 100 nm or less, particularly preferably 80 nm or less, and particularly preferably 50 nm or less. The thickness of the conductive layer 2 may be 10 nm or more, or 20 nm or more.

[0093] The anchoring force between the conductive layer 2 and the polarizing film 1 is, for example, 10.0 N / 25 mm or more, preferably 12.0 N / 25 mm or more, more preferably 14.0 N / 25 mm or more, and further preferably 18.0 N / 25 mm or more. The above-mentioned anchoring force can be measured by the following method. First, the polarizing film 10 with an adhesive layer as the evaluation object is cut into a 25 mm wide × 150 mm long piece as a test piece. Next, the entire surface of the polarizing film 1 possessed by the test piece is overlapped with the stainless steel test plate using double-sided tape, and a 2 kg roller is reciprocated once to press them together. Next, the adhesive layer 3 possessed by the test piece is overlapped with the evaluation piece, and a 2 kg roller is reciprocated once to press them together. The evaluation piece has a size of 30 mm wide × 150 mm long, and there is no particular limitation as long as it does not peel off from the adhesive layer 3 during the test. As an evaluation piece, for example, an ITO film (125 Tetlight OES (manufactured by Oike Industry Co., Ltd.) can be used. Next, using a commercially available tensile testing machine, the adhesive layer 3 and the conductive layer 2 were peeled off from the polarizing film 1 at a peeling angle of 180° and a tensile speed of 300 mm / min while holding the evaluation sheet, and the average value of the peeling force at this time was specified as the anchoring force between the conductive layer 2 and the polarizing film 1. It should be noted that the above test was carried out in an atmosphere of 23°C.

[0094] The surface resistivity of the conductive layer 2 and the above-mentioned loss A vary depending not only on the composition of the conductive material contained in the conductive layer 2 but also on the content of the conductive material in the conductive layer 2, the thickness of the conductive layer 2, and the like. Patent Documents 1 and 2 do not disclose any method for maintaining the surface resistivity of the conductive layer at 1.0×10 6 Ω / □ or less, and the loss A is adjusted to less than 0.9%. For example, Patent Document 1 discloses that when a coating composition for forming a conductive layer is applied to a transparent protective film, the measured values ​​of the total light transmittance are all about 98.5% or less (Examples 1-53). Based on this result, it can be expected that it is difficult to adjust the loss A to a value less than 1.5% for the solution of Patent Document 1.

[0095] [Adhesive layer]

[0096] The adhesive layer 3 is a layer containing an adhesive. Examples of the adhesive contained in the adhesive layer 3 include rubber adhesives, acrylic adhesives, silicone adhesives, urethane adhesives, vinyl alkyl ether adhesives, polyvinyl pyrrolidone adhesives, polyacrylamide adhesives, and cellulose adhesives. As the adhesive contained in the adhesive layer 3, acrylic adhesives are preferred from the perspectives of excellent optical transparency, appropriate adhesive properties such as wettability, cohesion, and adhesion, and excellent weather resistance, heat resistance, and the like.

[0097] The acrylic adhesive contains a (meth) acrylic polymer as a base polymer. The (meth) acrylic polymer contains, for example, a structural unit derived from a (meth) acrylic ester as a main component. In this specification, "(meth) acrylic acid" refers to acrylic acid and / or methacrylic acid. "Main component" refers to the structural unit with the largest content in the polymer on a weight basis.

[0098] The number of carbon atoms in the ester part (the part other than the (meth)acryloyl group) contained in the (meth)acrylate used to form the main skeleton of the (meth)acrylic polymer is not particularly limited, and is, for example, 1 to 18. The ester part of the (meth)acrylate may contain an aromatic ring such as a phenyl group or a phenoxy group, and may also contain an alkyl group. The alkyl group may be linear or branched. The (meth)acrylic polymer may contain one or more structural units derived from (meth)acrylate. In the (meth)acrylic polymer, the average value of the number of carbon atoms in the ester part contained in the structural unit derived from (meth)acrylate is preferably 3 to 9. From the viewpoints of adhesive properties, durability, adjustment of phase difference, adjustment of refractive index, etc., the (meth)acrylic polymer preferably has a structural unit derived from a (meth)acrylate containing an aromatic ring. By adjusting the phase difference of the adhesive layer 3 by a (meth)acrylate containing an aromatic ring, it is possible to suppress light leakage in the liquid crystal display device caused by the stretching of the adhesive layer 3 due to the thermal shrinkage of the polarizing film 1. In addition, the (meth)acrylate is suitable for adjusting the refractive index of the adhesive layer 3 to reduce the difference in refractive index between the adhesive layer 3 and the adherend (e.g., liquid crystal cell). If the difference in refractive index is reduced, the reflection of light at the interface between the adhesive layer 3 and the adherend is suppressed, and the visual recognition of the display can be improved.

[0099] Examples of the (meth)acrylate containing an aromatic ring include benzyl (meth)acrylate, phenyl (meth)acrylate, o-phenylphenol (meth)acrylate, phenoxy (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypropyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, ethylene oxide-modified nonylphenol (meth)acrylate, ethylene oxide-modified cresol (meth)acrylate, phenol ethylene oxide-modified (meth)acrylate, 2-hydroxy (meth)acrylate, (Meth)acrylates containing benzene rings, such as β-phenoxypropyl acrylate, methoxybenzyl (meth)acrylate, benzyl (meth)acrylate chloride, toluene (meth)acrylate, and styrene (meth)acrylate; (meth)acrylates containing naphthalene rings, such as hydroxyethylated β-naphthol acrylate, 2-naphthylethyl (meth)acrylate, 2-naphthyloxyethyl acrylate, and 2-(4-methoxy-1-naphthyloxy)ethyl (meth)acrylate; (meth)acrylates containing biphenyl rings, such as biphenyl (meth)acrylate, etc. Among these, benzyl (meth)acrylate and phenoxyethyl (meth)acrylate are preferred from the viewpoint of improving the adhesive properties and durability of the adhesive layer 3.

[0100] In the case where the refractive index of the adhesive layer 3 is adjusted by a (meth)acrylate containing an aromatic ring, the content of the structural unit derived from the (meth)acrylate containing an aromatic ring in all the constituent units of the (meth)acrylic polymer is preferably 3% by weight to 25% by weight. The content is more preferably 22% by weight or less, and further preferably 20% by weight or less. The content is more preferably 8% by weight or more, and further preferably 12% by weight or more. When the content of the structural unit derived from the (meth)acrylate containing an aromatic ring is 25% by weight or less, there is a tendency to suppress the light leakage of the liquid crystal display device caused by the shrinkage of the polarizing film 1 and to improve the reoperability of the adhesive layer 3. When the content is 3% by weight or more, there is a tendency to fully suppress the light leakage of the liquid crystal display device.

[0101] From the viewpoint of improving adhesion and heat resistance, the (meth)acrylic polymer may have, in addition to the above-mentioned structural units derived from the (meth)acrylate containing an aromatic ring, one or more structural units derived from a comonomer having a polymerizable functional group containing an unsaturated double bond, such as a (meth)acryloyl group or a vinyl group. Examples of the comonomer include hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl acrylate; carboxyl group-containing monomers such as (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid; acid anhydride group-containing monomers such as maleic anhydride and itaconic anhydride; caprolactone adducts of acrylic acid; sulfonic acid group-containing monomers such as styrenesulfonic acid, allylsulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidopropanesulfonic acid, propyl (meth)acrylate sulfonate, and (meth)acryloyloxynaphthalenesulfonic acid; and phosphoric acid group-containing monomers such as 2-hydroxyethylacryloyl phosphate.

[0102] Examples of the above-mentioned comonomers include (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N-butyl (meth)acrylamide, N-methylol (meth)acrylamide, N-methylolpropane (meth)acrylamide and other (N-substituted)amide monomers; (meth)acrylic acid alkylaminoalkyl ester monomers such as (meth)aminoethyl acrylate, (meth)acrylic acid N,N-dimethylaminoethyl ester, (meth)acrylic acid tert-butylaminoethyl ester; (meth)acrylic acid alkoxyalkyl ester monomers such as (meth)methoxyethyl acrylate, (meth)ethoxyethyl acrylate; N-(meth)acrylic acid Succinimide monomers such as acyloxymethylene succinimide, N-(meth)acryloyl-6-oxyhexamethylene succinimide, and N-(meth)acryloyl-8-oxyoctamethylene succinimide; morpholine monomers such as N-acryloylmorpholine; maleimide monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, and N-laurylitaconimide.

[0103] Examples of the comonomers include vinyl acetate, vinyl propionate, N-vinyl pyrrolidone, methyl vinyl pyrrolidone, vinyl pyridine, vinyl piperidone, vinyl pyrimidine, vinyl piperazine, vinyl pyrazine, vinyl pyrrole, vinyl imidazole, vinyl Vinyl monomers such as oxazole, vinyl morpholine, N-vinyl carboxylic acid amides, styrene, α-methylstyrene, N-vinyl caprolactam, etc.; cyanoacrylate monomers such as acrylonitrile and methacrylonitrile; epoxy group-containing acrylic monomers such as glycidyl (meth)acrylate; diol acrylate monomers such as polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate; acrylate monomers such as tetrahydrofurfuryl (meth)acrylate, fluorine-containing (meth)acrylate, silicone (meth)acrylate, 2-methoxyethyl acrylate, etc. In addition, as comonomers, olefin monomers such as isoprene, butadiene, isobutylene, etc.; ether group-containing vinyl monomers such as vinyl ether.

[0104] As the above-mentioned comonomers, for example, silane monomers such as 3-acryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 4-vinylbutyltrimethoxysilane, 4-vinylbutyltriethoxysilane, 8-vinyloctyltrimethoxysilane, 8-vinyloctyltriethoxysilane, 10-methacryloxydecyltrimethoxysilane, 10-acryloxydecyltrimethoxysilane, 10-methacryloxydecyltriethoxysilane, and 10-acryloxydecyltriethoxysilane can also be mentioned.

[0105] As the above-mentioned comonomer, for example, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, bisphenol A diglycidyl ether di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and the like can be used. Esterification products of (meth)acrylic acid and polyols such as acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate (multifunctional monomers having two or more unsaturated double bonds such as (meth)acryloyl groups and vinyl groups); compounds obtained by adding two or more compounds having unsaturated double bonds such as (meth)acryloyl groups and vinyl groups to the backbones of polyester, epoxy, urethane, etc. (for example, polyester (meth)acrylate, epoxy (meth)acrylate and urethane (meth)acrylate), etc.

[0106] The content of the structural unit derived from the comonomer in the (meth)acrylic polymer is not particularly limited, and is, for example, 0 wt % to 20 wt %, preferably 0.1 wt % to 15 wt %, and more preferably 0.1 wt % to 10 wt %.

[0107] As comonomers, hydroxyl-containing monomers and carboxyl-containing monomers are preferred from the viewpoint of adhesion and durability. As comonomers, hydroxyl-containing monomers and carboxyl-containing monomers can also be used in combination. For example, when the adhesive composition used to form the adhesive layer 3 contains a crosslinking agent, the comonomer functions as a reaction point with the crosslinking agent. As hydroxyl-containing monomers, carboxyl-containing monomers, etc., they are suitable for improving the cohesion and heat resistance of the obtained adhesive layer 3 due to their excellent reactivity with intermolecular crosslinking agents. In particular, hydroxyl-containing monomers are suitable for improving the reoperability of the adhesive layer 3. Carboxyl-containing monomers are suitable for taking into account both the durability and reoperability of the adhesive layer 3.

[0108] When a hydroxyl group-containing monomer is used as a comonomer, the content of the structural unit derived from the hydroxyl group-containing monomer in the (meth)acrylic polymer is preferably 0.01 wt% to 15 wt%, more preferably 0.03 wt% to 10 wt%, and further preferably 0.05 wt% to 7 wt%. When a carboxyl group-containing monomer is used as a comonomer, the content of the structural unit derived from the carboxyl group-containing monomer in the (meth)acrylic polymer is preferably 0.05 wt% to 10 wt%, more preferably 0.1 wt% to 8 wt%, and further preferably 0.2 wt% to 6 wt%.

[0109] The weight average molecular weight of the (meth)acrylic polymer is, for example, 500,000 to 3,000,000, and is preferably 700,000 to 2,700,000, and more preferably 800,000 to 2,500,000, from the viewpoint of durability, particularly heat resistance. When the weight average molecular weight of the (meth)acrylic polymer is 500,000 or more, the adhesive layer 3 tends to have sufficient heat resistance for practical use. When the weight average molecular weight of the (meth)acrylic polymer is 3,000,000 or less, the viscosity of the coating liquid used to prepare the adhesive layer 3 tends to be easily adjusted. If the viscosity of the coating liquid can be easily adjusted, it is not necessary to add a large amount of dilution solvent to the coating liquid, and therefore the manufacturing cost of the adhesive layer 3 can be suppressed. In this specification, the weight average molecular weight refers to a value obtained by converting the measurement result based on GPC (gel permeation chromatography) into polystyrene.

[0110] The (meth)acrylic polymer can be produced by known polymerization reactions such as solution polymerization, bulk polymerization, emulsion polymerization, various radical polymerizations, etc. The (meth)acrylic polymer may be a random copolymer, a block copolymer, or a graft copolymer.

[0111] The adhesive contained in the adhesive layer 3 may have a structure in which a base polymer is cross-linked by a cross-linking agent. For example, when a (meth) acrylic polymer is used as a base polymer, an organic cross-linking agent or a multifunctional metal chelate may be used as a cross-linking agent. As an organic cross-linking agent, for example, isocyanate cross-linking agents, peroxide cross-linking agents, epoxy cross-linking agents, imine cross-linking agents, etc. may be cited. A multifunctional metal chelate refers to a chelate formed by covalent bonding or coordinated bonding of a polyvalent metal to an organic compound. As atoms constituting the polyvalent metal, for example, Al, Cr, Zr, Co, Cu, Fe, Ni, V, Zn, In, Ca, Mg, Mn, Y, Ce, Sr, Ba, Mo, La, Sn, Ti, etc. may be cited. The organic compound contained in the multifunctional metal chelate may contain, for example, oxygen atoms, etc. As the organic compound, for example, alkyl esters, alcohol compounds, carboxylic acid compounds, ether compounds, ketone compounds, etc. may be cited.

[0112] In the pressure-sensitive adhesive, the amount of the crosslinking agent used is preferably 3 parts by weight or less, more preferably 0.01 to 3 parts by weight, further preferably 0.02 to 2 parts by weight, particularly preferably 0.03 to 1 part by weight, based on 100 parts by weight of the (meth)acrylic polymer.

[0113] The adhesive layer 3 may further include other materials other than the adhesive. As other materials, for example, conductive materials, silane coupling agents and other additives can be cited. The conductive material is suitable for reducing the surface resistivity of the adhesive layer 3 to prevent poor display caused by charging of the liquid crystal display device. As the conductive material, the conductive materials described above for the conductive layer 2 can be cited. From the viewpoint of compatibility with the base polymer and the transparency of the adhesive layer 3, the conductive material contained in the adhesive layer 3 is preferably an ionic compound. In particular, when the adhesive layer 3 includes an acrylic adhesive containing a (meth) acrylic polymer as a base polymer, an ionic compound is preferably used as the conductive material. From the viewpoint of antistatic performance, the ionic compound is preferably an ionic liquid.

[0114] The adhesive layer 3 preferably contains 0.05 to 20 parts by weight of a conductive material (e.g., an ionic compound) relative to 100 parts by weight of the base polymer of the adhesive (e.g., a (meth) acrylic polymer). By making the adhesive layer 3 contain 0.05 parts by weight or more of a conductive material, there is a tendency that the surface resistivity of the adhesive layer 3 is sufficiently reduced and the antistatic performance of the adhesive layer 3 is sufficiently improved. The adhesive layer 3 preferably contains 0.1 parts by weight or more of a conductive material, and more preferably contains 0.5 parts by weight or more, relative to 100 parts by weight of the base polymer of the adhesive. From the viewpoint of giving the adhesive layer 3 sufficient durability for practical use, the adhesive layer 3 preferably contains 20 parts by weight or less of a conductive material, and more preferably contains 10 parts by weight or less.

[0115] As other additives, for example, polyether compounds such as polyalkylene glycol (such as polypropylene glycol), colorants, pigments, dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, softeners, antioxidants, anti-aging agents, light stabilizers, ultraviolet absorbers, polymerization inhibitors, inorganic fillers, organic fillers, metal powders, etc. can be used appropriately according to the purpose of use. The additives can be in powder form, in particulate form, or in foil form. As additives, redox types can also be formed by using a reducing agent within a controllable range. By adding pigments such as colorants to the adhesive layer 3, it is sometimes possible to adjust the hue of the reflected light from the polarizing film 10 with an adhesive layer. Relative to 100 parts by weight of the base polymer of the adhesive (such as a (meth) acrylic polymer), the adhesive layer 3 preferably contains less than 5 parts by weight of other additives, more preferably less than 3 parts by weight, and further preferably less than 1 part by weight.

[0116] The thickness of the adhesive layer 3 is not particularly limited, and is, for example, 5 to 100 μm, and preferably 10 to 50 μm.

[0117] In the pressure-sensitive adhesive layer-attached polarizing film 10, the surface resistivity of the pressure-sensitive adhesive layer 3 is not particularly limited, but is less than 1.0×10 14 Ω / □ is sufficient, preferably 1.0×10 12 The lower limit of the surface resistivity of the adhesive layer 3 is not particularly limited, but is, for example, 1.0×10 8 Ω / □. The surface resistivity of the adhesive layer 3 can be measured by the same method as that of the conductive layer 2.

[0118] [Other layers]

[0119] The polarizing film 10 with an adhesive layer may further include other layers other than the polarizing film 1, the conductive layer 2 and the adhesive layer 3. The polarizing film 10 with an adhesive layer may include one or more other layers. For example, the other layer is arranged closer to the visible side than the polarizing film 1 and is in contact with the polarizing film 1. Examples of the other layers include: a surface treatment layer, a surface protection film and a phase difference film. Examples of the surface treatment layer include: a hard coating layer, an anti-glare treatment layer, an anti-reflection layer, an anti-adhesion layer, and the like.

[0120] As the material of the hard coat layer, for example, thermoplastic resins, materials cured by heat or radiation, etc. can be used. As materials cured by heat or radiation, for example, thermosetting resins; radiation-curing resins such as ultraviolet curing resins and electron beam curing resins can be cited. According to the ultraviolet curing resin, a cured resin layer can be formed efficiently by a curing treatment using ultraviolet irradiation with simple processing operations. As curable resins, for example, polyester resins, acrylic resins, carbamate resins, amide resins, silicone resins, epoxy resins, melamine resins, etc. can be cited. Curable resins include, for example, monomers, oligomers, polymers, etc. such as polyesters, acrylics, carbamates, amides, silicones, epoxies, and melamines. From the viewpoint of fast processing speed and less damage to the substrate caused by heat, the material of the hard coat layer is preferably a radiation-curing resin, and particularly preferably an ultraviolet curing resin. The ultraviolet curable resin preferably contains, for example, a compound having an ultraviolet-polymerizable functional group, particularly an acrylic monomer or oligomer having two or more, preferably 3 to 6, such functional groups. The ultraviolet curable resin is mixed with, for example, a photopolymerization initiator,

[0121] The anti-glare treatment layer and the anti-reflection layer are suitable for improving the visual recognition of the liquid crystal display device. The surface treatment layer has a hard coating layer and an anti-glare treatment layer or an anti-reflection layer, and the anti-glare treatment layer or the anti-reflection layer can be arranged closer to the visible side than the hard coating layer. The material of the anti-glare treatment layer is not particularly limited, for example, radiation-curable resins, thermosetting resins, thermoplastic resins, etc. can be used. As the material of the anti-reflection layer, for example: titanium oxide, zirconium oxide, silicon oxide, magnesium fluoride, etc. can be used. The surface treatment layer can have multiple anti-reflection layers.

[0122] The surface treatment layer can have conductivity by containing a conductive material. Examples of the conductive material include the conductive materials described above for the conductive layer 2.

[0123] The surface protection film can be arranged on the above-mentioned surface treatment layer, and can also be arranged on the polarizing film 1. The surface protection film, for example, has a support film, and an adhesive layer arranged on at least one side of the support film. The adhesive layer of the surface protection film may contain a light release agent, a conductive material, and the like. In the case where the adhesive layer of the surface protection film contains a conductive material, the surface protection film can be adhered to the surface treatment layer and then peeled off, so that the surface treatment layer contains a conductive material, and a conductive function is imparted to the surface. As the conductive material, the conductive materials described above for the conductive layer 2 can be listed. In order to impart a conductive function to the surface of the surface treatment layer by peeling off the surface protection film, it is preferred that the adhesive layer of the surface protection film contains a light release agent while containing the conductive material. As the light release agent, for example: silicone resins such as polyorganosiloxane can be listed. The conductive function imparted to the surface of the surface treatment layer can be appropriately adjusted by the amount of the conductive material and the light release agent used.

[0124] The other layer may include an easy-adhesion layer for improving the adhesion between the components. When the other layer is an easy-adhesion layer, the easy-adhesion layer may be disposed between the polarizing film 1 and the conductive layer 2. It should be noted that the surface of the conductive layer 2 side of the polarizing film 1 may be subjected to an easy-adhesion treatment such as a corona treatment or a plasma treatment instead of the easy-adhesion layer.

[0125] [Method for producing a polarizing film with an adhesive layer]

[0126] The polarizing film 10 with an adhesive layer can be produced, for example, by the following method. First, a solution or dispersion of a conductive material is prepared. The solvent of the solution or dispersion is, for example, water, and may further contain a water-soluble organic solvent. Examples of the water-soluble organic solvent include alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, tert-butanol, n-pentanol, isopentanol, sec-pentanol, tert-pentanol, 1-ethyl-1-propanol, 2-methyl-1-butanol, n-hexanol, and cyclohexanol.

[0127] Next, a solution or dispersion of a conductive material is applied to the surface of the polarizing film 1. The obtained coating film is dried to form the conductive layer 2 on the polarizing film 1. Thus, a laminate L including the polarizing film 1 and the conductive layer 2 can be obtained.

[0128] Next, a solution containing an adhesive is prepared. The solution is applied to the surface of the separator to obtain a coating film. The separator is not particularly limited, and for example, a polyethylene terephthalate film treated with a silicone release agent can be used. Next, the coating film is dried to form an adhesive layer 3 on the separator. By transferring the obtained adhesive layer 3 to the conductive layer 2 of the laminate L, a polarizing film 10 with an adhesive layer can be produced.

[0129] (Modification of the Polarizing Film with Pressure-Sensitive Adhesive Layer)

[0130] The polarizing film 10 with an adhesive layer may further include other components besides the polarizing film 1, the conductive layer 2 and the adhesive layer 3. Figure 2 As shown, the polarizing film 11 with an adhesive layer of this modification further includes an anti-reflection film 40. In the polarizing film 11 with an adhesive layer, the anti-reflection film 40, the polarizing film 1 and the adhesive layer 3 are arranged in the above-mentioned order in the stacking direction. The anti-reflection film 40 can be in contact with the polarizing film 1. Except for the anti-reflection film 40, the structure of the polarizing film 11 with an adhesive layer is the same as the structure of the polarizing film 10 with an adhesive layer. Therefore, the same reference symbols are marked for the common elements in the polarizing film 10 with an adhesive layer and the polarizing film 11 with an adhesive layer of the modification, and their descriptions are sometimes omitted. That is, the descriptions related to the following embodiments can be applied to each other as long as they are not technically contradictory. The following embodiments can also be combined with each other as long as they are not technically contradictory.

[0131] As an example, when the polarizing film 11 with an adhesive layer is laminated with the alkali-free glass in a state where the adhesive layer 3 is directly in contact with the alkali-free glass, light from the CIE standard light source D65 is incident from the surface opposite to the adhesive layer 3 (typically the surface of the anti-reflection film 40), reflected light with a light reflectance Y of less than 1.1% is generated. The polarizing film 11 with an adhesive layer that generates such reflected light is suitable for suppressing the reflection of light in the liquid crystal panel, thereby improving the visual recognition of the liquid crystal display device. It should be noted that the light reflectance Y refers to the Y value of the three stimulus values ​​(X, Y and Z) in the XYZ color system (CIE1931). The three stimulus values ​​are specified in detail in JIS Z8701:1999.

[0132] In detail, the above-mentioned light reflectance Y can be specified by the following method. First, the polarizing film 11 with an adhesive layer is adhered to the alkali-free glass using the adhesive layer 3. Alkali-free glass is a glass that does not substantially contain alkali components (alkali metal oxides). Specifically, the weight ratio of the alkali components in the glass is, for example, less than 1000 ppm, and further less than 500 ppm. The alkali-free glass is, for example, in the form of a plate and has a thickness of more than 0.5 mm. Next, a black film is adhered to the surface of the alkali-free glass on the opposite side of the surface adhered to the polarizing film 11 with an adhesive layer. Next, light from the CIE standard light source D65 is incident on the surface of the polarizing film 11 with an adhesive layer on the side of the anti-reflection film 40 at an incident angle of 5°. The spectral reflectance within the wavelength range of 360nm to 740nm of the mirror reflected light generated at this time can be specified, and the light reflectance Y in the XYZ color system (CIE1931) can be specified based on the spectral reflectance.

[0133] The light reflectance Y is preferably 1.0% or less, more preferably 0.9% or less, further preferably 0.8% or less, and particularly preferably 0.7% or less. The lower limit of the light reflectance Y is not particularly limited, and is, for example, 0.1%.

[0134] The reflected light above is * a * b * a in the color system (CIE1976) * Value and b * The value is not particularly limited, but preferably satisfies the following relational expressions (1) and (2).

[0135] -10≤a * ≤10 (1)

[0136] -18≤b * ≤5 (2)

[0137] The above a * Value and b * The value can be specified by the following formulas (i) and (ii) specified in JIS Z8781-4:2013 using tristimulus values ​​(X, Y, and Z) of reflected light in an XYZ color system.

[0138] [Mathematical formula 1]

[0139] a * =500[f(X / X n )-f(Y / Y n )] (i)

[0140] b * =200[f(Y / Y n )-f(Z / Z n (ii)

[0141] The above a * The value is preferably -6 or more and 6 or less, and more preferably -3 or more and 3 or less. * The value is preferably -15 to 3, more preferably -10 to 2, further preferably -6 to 2, and particularly preferably -5 to 2. * Value and b * The values ​​may also satisfy the following relations (3) and (4).

[0142] b * ≥-1.5a * -15 (3)

[0143] b * ≤-1.5a * +7.5 (4)

[0144] In addition, a * Value and b * The values ​​may also satisfy the following equations (5) and (6).

[0145] b * ≥-1.5a * -5 (5)

[0146] b * ≤-1.5a * +4.5 (6)

[0147] The L of the reflected light * The value is, for example, 12 or less, preferably 10 or less, more preferably 8 or less, and further preferably 7 or less. * The lower limit of the value is not particularly limited, and is, for example, 3. * The value can be specified according to the following formula (iii) specified in JIS Z 8781-4:2013 using the above-mentioned tristimulus values.

[0148] [Mathematical formula 2]

[0149] L * =116f(Y / Y n )-16 (iii)

[0150] Meet L * Value = 0, a * Value = 0 and b * The color difference ΔE between the light having a color value of 0 (light having a completely natural hue) and the above-mentioned reflected light is, for example, 22 or less, preferably 18 or less, more preferably 15 or less, further preferably 10 or less, and particularly preferably 8 or less. The lower limit of the color difference ΔE is not particularly limited, and is, for example, 3. The color difference ΔE can be calculated using the L value of the reflected light.* Value, a * Value and b * The value was calculated based on the following formula (iv).

[0151] ΔE * ={(L * ) 2 +(a * ) 2 +(b * ) 2} 1 / 2 (iv)

[0152] [Anti-reflective film]

[0153] like Figure 3 As shown, the anti-reflection film 40 has a first high refractive index layer 41, a first low refractive index layer 42, a second high refractive index layer 43 and a second low refractive index layer 44 in the stacking direction. The first high refractive index layer 41 is, for example, in contact with the polarizing film 1. The second low refractive index layer 44 is, for example, located closest to the visible side among these layers.

[0154] The high refractive index layers 41 and 43 are layers having a higher refractive index than the low refractive index layers 42 and 44, and their refractive indexes are, for example, in the range of 1.6 to 3.2. The refractive index of the first high refractive index layer 41 may be the same as or different from that of the second high refractive index layer 43. In this specification, unless otherwise specified, "refractive index" refers to a value measured at a temperature of 25°C using light of a wavelength λ=550nm and in accordance with the provisions of JIS K0062:1992.

[0155] In a preferred embodiment of the present invention, the high refractive index layers 41 and 43, for example, contain a binder resin and inorganic particles dispersed in the binder resin. The binder resin is typically a cured product of an ionizing radiation-curable resin, more specifically, a cured product of an ultraviolet-curable resin. As ultraviolet-curable resins, resins containing polymers or oligomers having substituents capable of free radical polymerization can be cited, such as (meth)acrylate resins. (Meth)acrylate resins as ultraviolet-curable resins include polymers or oligomers such as epoxy (meth)acrylate, polyester (meth)acrylate, acrylic (meth)acrylate, and ether (meth)acrylate. In addition to the above-mentioned polymers or oligomers, the (meth)acrylate resin may further contain a free radical polymerizable monomer (precursor). The molecular weight of the monomer is, for example, 200 to 700. Specific examples of the monomer include pentaerythritol triacrylate (PETA: molecular weight 298), neopentyl glycol diacrylate (NPGDA: molecular weight 212), dipentaerythritol hexaacrylate (DPHA: molecular weight 632), dipentaerythritol pentaacrylate (DPPA: molecular weight 578), and trimethylolpropane triacrylate (TMPTA: molecular weight 296). The ionizing radiation curable resin may contain an initiator as required. Examples of the initiator include UV free radical generators (IRGACURE 907, IRGACURE 127, IRGACURE 192, etc. manufactured by Ciba Specialty Chemicals) and benzoyl peroxide. The above-mentioned binder resin may contain other resins in addition to the cured product of the ionizing radiation curable resin. The other resins may be thermosetting resins or thermoplastic resins. Examples of other resins include aliphatic resins (e.g., polyolefins), urethane resins, and the like.

[0156] The refractive index of the binder resin is, for example, 1.40 to 1.60. The amount of the binder resin blended is, for example, 10 to 80 parts by weight, or preferably 20 to 70 parts by weight, based on 100 parts by weight of the high refractive index layer to be formed.

[0157] The material of the inorganic fine particles is, for example, a metal oxide. Specific examples of metal oxides include zirconium oxide (refractive index: 2.19), aluminum oxide (refractive index: 1.56 to 2.62), titanium oxide (refractive index: 2.49 to 2.74), and silicon oxide (refractive index: 1.25 to 1.46). These metal oxides not only have low light absorption, but also have a higher refractive index than organic materials such as ionizing radiation curing resins and thermoplastic resins, and are therefore suitable for adjusting the refractive index of the high refractive index layers 41 and 43. The inorganic fine particles preferably contain zirconium oxide or titanium oxide.

[0158] The refractive index of the inorganic particles is, for example, 1.60 or more, preferably 1.70 to 2.80, and more preferably 2.00 to 2.80. Inorganic particles having a refractive index of 1.60 or more are suitable for adjusting the refractive index of the high refractive index layers 41 and 43. The average particle size of the inorganic particles is, for example, 1 nm to 100 nm, preferably 10 nm to 80 nm, and more preferably 20 nm to 70 nm. The average particle size of the inorganic particles refers to the particle size (d50) equivalent to 50% of the volume accumulation in the particle size distribution measured by, for example, a laser diffraction particle size analyzer.

[0159] The inorganic particles may not be surface-modified, but are preferably surface-modified. The surface-modified inorganic particles tend to be well dispersed in the binder resin. The surface modification is performed, for example, by coating a surface modifier on the surface of the inorganic particles to form a surface modifier layer. Examples of the surface modifier include coupling agents such as silane coupling agents and titanate coupling agents; and surfactants such as fatty acid surfactants. If such a surface modifier is used, the wettability of the binder resin and the inorganic particles is improved, and there is a tendency for the interface between the binder resin and the inorganic particles to be stabilized.

[0160] The amount of inorganic particles is, for example, 10 to 90 parts by weight, more preferably 20 to 80 parts by weight, relative to 100 parts by weight of the high refractive index layer formed. When the amount of inorganic particles is within the above range, the antireflection film has sufficient mechanical properties and tends to be able to sufficiently reduce the light reflectance ratio Y of the reflected light.

[0161] The refractive index of the high refractive index layers 41 and 43 including the binder resin and the inorganic fine particles is, for example, 1.6 to 2.6, or preferably 1.7 to 2.2.

[0162] In another preferred embodiment of the present invention, the high refractive index layers 41 and 43 include metal oxides or metal nitrides, and are preferably substantially formed of metal oxides or metal nitrides. Specific examples of metal oxides include titanium oxide (TiO2), indium / tin oxide (ITO), niobium oxide (Nb2O5), yttrium oxide (Y2O3), indium oxide (In2O3), tin oxide (SnO2), zirconium oxide (ZrO2), hafnium oxide (HfO2), antimony oxide (Sb2O3), tantalum oxide (Ta2O5), zinc oxide (ZnO), and tungsten oxide (WO3). As a specific example of metal nitrides, silicon nitride (Si3N4) can be cited. The high refractive index layers 41 and 43 preferably include niobium oxide (Nb2O5) or titanium oxide (TiO2). The refractive index of the high refractive index layer composed of metal oxides or metal nitrides is, for example, 2.00 to 2.60, preferably 2.10 to 2.45.

[0163] The material of the first high refractive index layer 41 may be the same as or different from that of the second high refractive index layer 43 .

[0164] The physical film thickness of the first high refractive index layer 41 is, for example, 9 nm to 15 nm, preferably 11 nm to 13 nm. The optical film thickness of the first high refractive index layer 41 is, for example, 20 nm to 35 nm, preferably 25 nm to 30 nm. It should be noted that in this specification, the optical film thickness is a value represented by the product of the refractive index of light with a wavelength of 550 nm and the physical film thickness.

[0165] The physical film thickness of the second high refractive index layer 43 is, for example, 98 nm to 124 nm, or preferably 111 nm to 120 nm. The optical film thickness of the second high refractive index layer 43 is, for example, 230 nm to 290 nm, or preferably 260 nm to 280 nm.

[0166] The low refractive index layers 42 and 44 are layers having a refractive index lower than that of the high refractive index layers 41 and 43, and their refractive indexes are, for example, 1.35 to 1.55, preferably 1.40 to 1.50. By appropriately adjusting the difference in refractive index between the low refractive index layers 42 and 44 and the high refractive index layers 41 and 43, there is a tendency to suppress the reflection of light. The refractive index of the first low refractive index layer 42 may be the same as or different from that of the second low refractive index layer 44.

[0167] As the material of low refractive index layer 42 and 44, for example, metal oxide and metal fluoride can be cited. As the specific example of metal oxide, silicon oxide (SiO2) can be cited. As the specific example of metal fluoride, magnesium fluoride and fluosilicic acid can be cited. From the viewpoint of refractive index, the material of low refractive index layer 42 and 44 is preferably magnesium fluoride and fluosilicic acid, and from the viewpoints of ease of manufacture, mechanical strength, moisture resistance, etc., silicon oxide is preferably used. If various characteristics are considered comprehensively, silicon oxide is preferably used. The material of the first low refractive index layer 42 can be the same as or different from the second low refractive index layer 44.

[0168] The material of the low refractive index layers 42 and 44 can be a cured product of a curable fluorine-containing resin. The curable fluorine-containing resin, for example, has a structural unit from a fluorine-containing monomer and a structural unit from a cross-linking monomer. As specific examples of fluorine-containing monomers, for example: fluoroolefins (vinyl fluoride, vinylidene fluoride, tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoro-2,2-dimethyl-1,3-dioxole, etc.), (meth)acrylate derivatives with partially or completely fluorinated alkyl groups (Viscoat 6FM (manufactured by Osaka Organic Chemical Co., Ltd.), M-2020 (manufactured by Daikin Co., Ltd.), etc.), completely or partially fluorinated vinyl ethers, etc. As cross-linking monomers, for example: (meth)acrylate monomers having cross-linking functional groups in the molecule such as glycidyl methacrylate; (meth)acrylate monomers having functional groups such as carboxyl, hydroxyl, amino, and sulfonic acid groups ((meth)acrylic acid, hydroxymethyl (meth)acrylate, (meth)acrylate hydroxyalkyl ester, (meth)acrylate allyl ester, etc.). The fluorine-containing resin may have a structural unit derived from other monomers (for example, an olefin monomer, a (meth)acrylate monomer, or a styrene monomer) other than the above-mentioned compounds.

[0169] The physical film thickness of the first low refractive index layer 42 is, for example, 26 nm to 34 nm, or preferably 27 nm to 31 nm. The optical film thickness of the first low refractive index layer 42 is, for example, 38 nm to 50 nm, or preferably 40 nm to 45 nm.

[0170] The physical film thickness of the second low refractive index layer 44 is, for example, 68 nm to 88 nm, or preferably 72 nm to 79 nm. The optical film thickness of the second low refractive index layer 44 is, for example, 100 nm to 128 nm, or preferably 105 nm to 115 nm.

[0171] The preparation method of the high refractive index layer and the low refractive index layer is not particularly limited. When these layers contain resins, these layers can be formed by a so-called wet process (curing after applying the resin composition). When these layers are composed of metal oxides, metal fluorides, metal nitrides, etc., these layers can be formed by a so-called dry process. As specific examples of dry processes, PVD (physical vapor deposition, Physical Vapor Deposition) method and CVD (chemical vapor deposition, Chemical Vapor Deposition) method can be cited. As a PVD method, for example: vacuum evaporation method, reactive evaporation method, ion beam assisted method, sputtering method, ion plating method can be cited. As a CVD method, for example, a plasma CVD method can be cited. From the viewpoint of reducing the deviation of the hue of the reflected light, as a dry process, sputtering method is preferred.

[0172] Figure 3The anti-reflection film 40 may further include other components besides the high refractive index layer and the low refractive index layer. Figure 4 Another example of the antireflection film is shown. Figure 4 The anti-reflection film 47 further includes a substrate 45 and an adhesive layer 46. The substrate 45 is, for example, disposed between the first high refractive index layer 41 and the polarizing film 1, and is in contact with the first high refractive index layer 41. The adhesive layer 46 is, for example, disposed between the substrate 45 and the polarizing film 1, and is in contact with the substrate 45 and the polarizing film 1, respectively.

[0173] The substrate 45 includes, for example, a transparent resin film. Examples of the material of such a resin film include cellulose resins (cellulose triacetate, cellulose diacetate, cellulose propionate, cellulose butyrate, cellulose acetate propionate, nitrocellulose, etc.), polyamide resins (nylon-6, nylon-66, etc.), polyimide resins, polycarbonate resins, polyester resins (polyethylene terephthalate, polyethylene naphthalate, polyethylene 1,4-cyclohexanedimethanol terephthalate, polyethylene-1,2-diphenoxyethane-4,4'-dicarboxylate, polybutylene terephthalate, etc.), polyolefin resins (polyethylene, polypropylene, polymethylpentene, etc.), polysulfone resins, polyethersulfone resins, polyarylate resins, polyetherimide resins, polymethyl methacrylate resins, polyetherketone resins, polystyrene resins, polyvinyl chloride resins, polyvinyl alcohol resins, ethylene vinyl alcohol resins, (meth)acrylic resins, (meth)acrylonitrile resins, etc. The substrate 45 may be a single resin film layer, a laminate of multiple resin films, or a laminate of a resin film and a hard coating layer described later. The substrate 45 may contain additives. Specific examples of additives include antistatic agents, ultraviolet absorbers, plasticizers, lubricants, colorants, antioxidants, flame retardants, and the like.

[0174] In a preferred embodiment of the present invention, the substrate 45 is a triacetyl cellulose (TAC) film. The triacetyl cellulose film can also function as a protective film for the polarizer. Therefore, by using the anti-reflection film 47 having the substrate 45 formed of the triacetyl cellulose film, the transparent protective film on the visible side of the polarizing film 1 can sometimes be omitted.

[0175] In another preferred embodiment of the present invention, the substrate 45 includes a hard coating layer. The substrate 45 may be composed of a hard coating layer, or may be a laminate of a resin film and a hard coating layer. The hard coating layer is, for example, a cured layer of an ionizing radiation curable resin. As ionizing radiation, for example, ultraviolet rays, visible light, infrared rays, electron beams, preferably ultraviolet rays. That is, the ionizing radiation curable resin is preferably an ultraviolet curable resin. As ultraviolet curable resins, for example, (meth) acrylic resins, silicone resins, polyester resins, carbamate resins, amide resins, epoxy resins, etc. may be mentioned. As (meth) acrylic resins, for example, a cured product (polymer) formed by ultraviolet curing of a multifunctional monomer containing a (meth) acryloyloxy group. For example, one multifunctional monomer may be used or two or more may be used in combination. For example, the multifunctional monomer may be mixed with a photopolymerization initiator.

[0176] Inorganic particles or organic particles may be dispersed in the hard coating layer. The average particle size (d50) of the particles is, for example, 0.01 μm to 3 μm. As particles dispersed in the hard coating layer, silicon oxide (SiO2) is preferred from the viewpoints of refractive index, stability, heat resistance, etc. The hard coating layer may contain additives. Specific examples of additives include leveling agents, fillers, dispersants, plasticizers, ultraviolet absorbers, surfactants, antioxidants, and thixotropic agents. In addition, a concavo-convex shape may be formed on the surface of the hard coating layer. The hard coating layer having a concavo-convex shape on the surface has a light diffusion function (anti-glare).

[0177] The physical film thickness of the substrate 45 is not particularly limited. When the substrate 45 is a single resin film layer or a laminate of multiple resin films, the physical film thickness of the substrate 45 is, for example, in the range of 10 μm to 200 μm. When the substrate 45 includes a hard coating layer, the physical film thickness of the hard coating layer is, for example, in the range of 1 μm to 50 μm.

[0178] The refractive index of the substrate 45 (when the substrate 45 has a laminated structure, the refractive index of the layer closest to the first high refractive index layer 41 ) is, for example, 1.3 to 1.8, or preferably 1.4 to 1.7.

[0179] The adhesive layer 46 is a layer containing an adhesive. Examples of the adhesive contained in the adhesive layer 46 include resins having adhesive properties. Examples of such resins include acrylic resins, acrylic urethane resins, urethane resins, and silicone resins. The adhesive layer 46 preferably contains an acrylic adhesive composed of an acrylic resin.

[0180] The adhesive layer 46 may further contain additives as required. Examples of the additives include crosslinking agents, tackifiers, plasticizers, pigments, dyes, fillers, anti-aging agents, conductive materials, ultraviolet absorbers, light stabilizers, release regulators, softeners, surfactants, flame retardants, antioxidants, and the like. Examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, peroxide crosslinking agents, melamine crosslinking agents, urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, carbodiimide crosslinking agents, Oxazoline crosslinking agents, aziridine crosslinking agents, amine crosslinking agents, etc.

[0181] The physical film thickness of the adhesive layer 46 is, for example, 5 μm to 100 μm, or preferably 10 μm to 50 μm.

[0182] The anti-reflection film 47 may further include other components besides the substrate 45 and the adhesive layer 46. For example, the anti-reflection film 47 may further include an anti-glare layer disposed between the substrate 45 and the first high refractive index layer 41. The anti-reflection film 47 may further include an adhesive layer disposed between specific components (for example, between the substrate 45 and the first high refractive index layer 41, or between the anti-glare layer and the first high refractive index layer 41). The adhesive layer is a layer that improves the adhesion between components, and may include, for example, silicon, SiO x (x<2) The physical film thickness of the adhesion layer is, for example, 1 nm to 10 nm, preferably 2 nm to 5 nm. The refractive index of the adhesion layer is, for example, 1 to 2.5.

[0183] The anti-reflection films 40 and 47 may further include an antifouling layer disposed closer to the visible side than the second low refractive index layer 44 and in contact with the second low refractive index layer 44. The antifouling layer is a layer having an antifouling effect, and for example, contains at least one selected from fluorine resins and silicone resins. The physical film thickness of the antifouling layer is, for example, 5 nm to 13 nm, preferably 5 nm to 10 nm. The refractive index of the antifouling layer is, for example, 1 to 2.

[0184] It is preferable that the reflected light generated when the CIE standard light source D65 is incident on the anti-reflection films 40 and 47 is L * a * b * a1 in the color system * Value and b1 * The absolute value of a1 is small. * The value is, for example, -6 to 6, more preferably -3 to 3. b1 * The value is, for example, -15 to 3, preferably -10 to 2, and more preferably -5 to 2. a1 * Value and b1 *The value can be specified by the following method. First, the first high refractive index layer 41, the first low refractive index layer 42, the second high refractive index layer 43 and the second low refractive index layer 44 of the anti-reflection film 40 are stacked on the black film in the above order, or the anti-reflection film 47 is adhered to the black film through the adhesive layer 46 of the anti-reflection film 47. Next, light from the CIE standard light source D65 is incident on the surface of the anti-reflection film 40 or 47 on the side of the second low refractive index layer at an incident angle of 5°. The spectral reflectance in the wavelength range of 360nm to 740nm of the mirror reflected light generated at this time is specified, and the tristimulus values ​​in the XYZ color system are specified based on the spectral reflectance. Using the obtained tristimulus values, a1 is specified by the above formulas (i) and (ii). * Value and b1 * value.

[0185] The light reflectance Y1 of the reflected light is, for example, 0.3% or less, or preferably 0.2% or less.

[0186] (Other Modifications of the Polarizing Film with Pressure-Sensitive Adhesive Layer)

[0187] The polarizing film 11 with an adhesive layer may further include other components other than the above components. Figure 5 As shown, the polarizing film 12 with an adhesive layer of this modification further includes a transparent substrate 50 and an adhesive layer 55 disposed between the antireflection film 40 and the polarizing film 1. Except for the transparent substrate 50 and the adhesive layer 55, the structure of the polarizing film 12 with an adhesive layer is the same as that of the polarizing film 11 with an adhesive layer.

[0188] The transparent substrate 50 is in contact with the first high refractive index layer 41 of the antireflection film 40, for example. However, the polarizing film 12 with an adhesive layer may also have Figure 4 The anti-reflection film 47 described above is used instead of the anti-reflection film 40. At this time, the adhesive layer 46 of the anti-reflection film 47 is in contact with the transparent substrate 50. The adhesive layer 46 is, for example, disposed between the transparent substrate 50 and the polarizing film 1 and is in contact with the transparent substrate 50 and the polarizing film 1, respectively.

[0189] As the transparent substrate 50, those exemplified as the first transparent substrate 6 and the second transparent substrate 7 included in the liquid crystal cell 20 described later can be used. The transparent substrate 50 is preferably made of glass. In this specification, the transparent substrate 50 made of glass may be referred to as "cover glass".

[0190] As the adhesive layer 55, the adhesive layer described above for the adhesive layer 3 can be used. It is particularly preferred that the adhesive layer 55 includes a commercially available optically clear adhesive (OCA: Optical Clear Adhesive). The adhesive layer 55 can be formed using, for example, an adhesive tape such as LUCIACS (registered trademark) CS9621T.

[0191] (Embodiment of Liquid Crystal Panel)

[0192] like Figure 6 As shown, the liquid crystal panel 100 includes a polarizing film 10 with an adhesive layer and a liquid crystal unit 20. In the liquid crystal panel 100, a polarizing film 11 or 12 with an adhesive layer may be used instead of the polarizing film 10 with an adhesive layer. The polarizing film 10 with an adhesive layer is directly or indirectly connected to the liquid crystal unit 20. For example, no further conductive layer, such as an ITO layer, is provided between the polarizing film 10 with an adhesive layer and the liquid crystal unit 20. Other layers other than the conductive layer may be arranged between the polarizing film 10 with an adhesive layer and the liquid crystal unit 20. The liquid crystal unit 20 may be bonded to the adhesive layer 3 of the polarizing film 10 with an adhesive layer, or may be directly connected to the polarizing film 10 with an adhesive layer.

[0193] The liquid crystal cell 20 includes, for example, a liquid crystal layer 5, a first transparent substrate 6, and a second transparent substrate 7. The liquid crystal layer 5 is, for example, disposed between the first transparent substrate 6 and the second transparent substrate 7, and is in contact with the first transparent substrate 6 and the second transparent substrate 7, respectively. The first transparent substrate 6 is, for example, in contact with the adhesive layer 3 of the polarizing film 10 with an adhesive layer. The liquid crystal cell 20 does not include, for example, an ITO layer between the first transparent substrate 6 and the adhesive layer 3 of the polarizing film 10 with an adhesive layer. In other words, the liquid crystal panel 100 does not include, for example, an ITO layer between the first transparent substrate 6 and the adhesive layer 3.

[0194] The liquid crystal layer 5 includes, for example, liquid crystal molecules that are uniformly oriented in the absence of an electric field. The liquid crystal layer 5 including such liquid crystal molecules is suitable for an IPS (In-Plane-Switching) method. However, the liquid crystal layer 5 can also be used for a TN (Twisted Nematic) type, an STN (Super Twisted Nematic) type, a π type, a VA (Vertical Alignment) type, etc. The thickness of the liquid crystal layer 5 is, for example, 1.5 μm to 4 μm.

[0195] As materials of the first transparent substrate 6 and the second transparent substrate 7, glass and polymers may be cited, for example. In this specification, a transparent substrate composed of a polymer may be referred to as a polymer film. As polymers constituting the transparent substrate, for example, polyethylene terephthalate, polycycloolefin, polycarbonate, etc. may be cited. The thickness of a transparent substrate composed of glass may be, for example, 0.1 mm to 1 mm. The thickness of a transparent substrate composed of a polymer may be, for example, 10 μm to 200 μm.

[0196] The liquid crystal cell 20 may further include other layers other than the liquid crystal layer 5, the first transparent substrate 6, and the second transparent substrate 7. Examples of other layers include a color filter, an easy-adhesion layer, and a hard coating layer. The color filter is, for example, disposed closer to the visible side than the liquid crystal layer 5, preferably between the first transparent substrate 6 and the adhesive layer 3 of the polarizing film 10 with an adhesive layer. The easy-adhesion layer and the hard coating layer are, for example, disposed on the surface of the first transparent substrate 6 or the second transparent substrate 7.

[0197] The liquid crystal panel 100 may further include a conductive structure (not shown) electrically connected to the side of the conductive layer 2. The conductive structure may be grounded to further suppress the polarizing film 10 with the adhesive layer from being charged by static electricity. The conductive structure may cover the entire side of the conductive layer 2 or partially cover the side of the conductive layer 2. The ratio of the area of ​​the side of the conductive layer 2 covered by the conductive structure to the area of ​​the entire side of the conductive layer 2 is, for example, 1% or more, preferably 3% or more. The conductive structure may be electrically connected not only to the side of the conductive layer 2, but also to the side of the polarizing film 1 and the adhesive layer 3.

[0198] Examples of materials for the conductive structure include conductive pastes made of metals such as silver and gold, conductive adhesives, and other conductive materials. The conductive structure may be wiring extending from the side surface of the conductive layer 2 .

[0199] The liquid crystal panel 100 may further include other optical films other than the polarizing film 1. Examples of other optical films include polarizing films, reflective plates, anti-transmission plates, phase difference films, viewing angle compensation films, brightness enhancement films, and other films used in liquid crystal display devices. Phase difference films include, for example, 1 / 2 wave plates and 1 / 4 wave plates. The liquid crystal panel 100 may further include one or more other optical films among these.

[0200] When the other optical film is a polarizing film, the polarizing film is bonded to the second transparent substrate 7 of the liquid crystal unit 20 via an adhesive layer, for example. The polarizing film has, for example, the structure described above for the polarizing film 1. In the polarizing film as the other optical film, the transmission axis (or absorption axis) of the polarizer is, for example, orthogonal to the transmission axis (or absorption axis) of the polarizer in the polarizing film 1. As the material of the adhesive layer for bonding the polarizing film to the second transparent substrate 7, the material described above for the adhesive layer 3 can be used. The thickness of the adhesive layer is not particularly limited, and is, for example, 1 to 100 μm, preferably 2 to 50 μm, more preferably 2 to 40 μm, and further preferably 5 to 35 μm.

[0201] The liquid crystal panel 100 having a polarizing film 10 with an adhesive layer shows good results when an ESD (Electro-Static Discharge) test is performed. The ESD test is implemented, for example, by the following method. First, the liquid crystal panel 100 is set on a backlight device. Next, static electricity is applied to the visible side (polarizing film 1 side) of the liquid crystal panel 100. Static electricity is applied using an electrostatic discharge gun (Electrostaticdischarge Gun) whose applied voltage is adjusted to 15kV. When static electricity is applied, white spots appear on a part of the liquid crystal panel 100. The time T from the time the static electricity is applied until the white spots disappear is measured. For the liquid crystal panel 100, the time T is, for example, less than 10 seconds, preferably less than 1 second, and more preferably less than 0.5 seconds. It should be noted that the ESD test is carried out under the conditions of 23°C and 55% RH.

[0202] The liquid crystal panel 100 is suitable for applications that do not require a touch sensor, such as an instrument cluster and a mirror display for a vehicle. The instrument cluster is a panel that displays the vehicle's running speed, engine speed, and the like.

[0203] (Modification of Liquid Crystal Panel)

[0204] Figure 6 The liquid crystal panel 100 may further include a touch sensor or a touch panel. Figure 7 The liquid crystal panel 110 is shown to include a touch panel 30. The structure of the liquid crystal panel 110 is the same as that of the liquid crystal panel 100 except for the touch panel 30. Therefore, the same reference numerals are used to indicate the common elements of the liquid crystal panel 100 and the liquid crystal panel 110, and their description may be omitted.

[0205] In the liquid crystal panel 110, the touch panel 30 is, for example, arranged closer to the visible side than the polarizing film 1. The touch panel 30 is not in contact with the polarizing film 10 with an adhesive layer, and a gap (air layer) is formed between the touch panel 30 and the polarizing film 10 with an adhesive layer. The liquid crystal panel 110 is a so-called out-cell type liquid crystal panel. As the touch panel 30, an optical method, an ultrasonic method, an electrostatic capacitance method, a resistive film method, etc. can be adopted. In the case where the touch panel 30 is a resistive film method, the touch panel 30 has, for example, a structure in which two electrode plates having a transparent conductive film are arranged in a manner opposite to each other with a spacer therebetween. In the case where the touch panel 30 is a capacitive method, the touch panel 30 is, for example, composed of a transparent conductive film having a transparent conductive film having a given pattern shape.

[0206] (Embodiment of Liquid Crystal Display Device)

[0207] The liquid crystal display device of this embodiment includes, for example, a liquid crystal panel 100 and a lighting system. Figure 7 The liquid crystal panel 110 described above replaces the liquid crystal panel 100. In the liquid crystal display device, the liquid crystal panel 100 is disposed, for example, on the visible side relative to the lighting system. The lighting system includes, for example, a backlight or a reflector, and irradiates the liquid crystal panel 100 with light.

[0208] Example

[0209] The present invention is described in more detail below by way of examples. The present invention is not limited to the examples shown below. It should be noted that, below, unless otherwise specified, "%" means "weight %", "parts" means "parts by weight", and "thickness" means "physical film thickness". Unless otherwise specified, the indoor temperature and humidity are 23°C and 65%RH.

[0210] <Weight average molecular weight of (meth)acrylic polymer>

[0211] In the following examples, the weight average molecular weight (Mw) of the (meth)acrylic polymer was measured by GPC (gel permeation chromatography). Mw / Mn of the (meth)acrylic polymer was also measured in the same manner.

[0212] ·Analysis device: Made by Tosoh Corporation, HLC-8120GPC

[0213] ·Chromatographic column: G7000H manufactured by Tosoh Corporation XL +GMH XL +GMH XL

[0214] ·Column size: 7.8mmφ×30cm each, 90cm in total

[0215] Column temperature: 40℃

[0216] Flow rate: 0.8mL / min

[0217] Injection volume: 100μL

[0218] ·Eluent: Tetrahydrofuran

[0219] Detector: Differential Refractometer (RI)

[0220] Standard sample: polystyrene

[0221] <Examples and Comparative Examples of Polarizing Films with Pressure-Sensitive Adhesive Layers Not Having an Antireflection Film>

[0222] (Example 1)

[0223] [TAC film with hard coating]

[0224] First, a resin solution (manufactured by DIC Corporation, trade name: UNIDIC 17-806, solid content concentration: 80%) obtained by dissolving an ultraviolet curable resin monomer or oligomer containing urethane acrylate as the main component in butyl acetate was prepared. 5 parts of a photopolymerization initiator (manufactured by BASF, trade name: IRGACURE907) and 0.1 parts of a leveling agent (manufactured by DIC Corporation, trade name: GRANDIC PC4100) were added to the resin solution relative to 100 parts of the solid content of the resin solution. Next, cyclopentanone and propylene glycol monomethyl ether were added to the resin solution at a weight ratio of 45:55 so that the solid content concentration in the resin solution was adjusted to 36%. A hard coating forming material was thus prepared. The obtained forming material was applied to a transparent protective film containing triacetyl cellulose (TAC film manufactured by Konica Minolta Co., Ltd., trade name "KC4UY") with a thickness of 40 μm to form a coating film. At this time, the thickness of the coating film was adjusted so that the thickness of the hard coating layer obtained by curing the forming material was adjusted to 7 μm. Next, the coating film was dried at 90° C. for 1 minute, and further irradiated with a high-pressure mercury lamp at a cumulative light intensity of 300 mJ / cm 2 Thus, the coating film is cured to obtain a TAC film with a hard coating layer (HC).

[0225] [Polarizing film]

[0226] First, a polyvinyl alcohol film with a thickness of 80 μm was dyed in a 0.3% iodine solution (temperature 30°C) for 1 minute between multiple rollers with different speed ratios, and stretched to a stretch ratio of 3 times. Next, the obtained stretched film was immersed in an aqueous solution (temperature 60°C) with a boric acid concentration of 4% and a potassium iodide concentration of 10% for 0.5 minutes, and stretched to a total stretch ratio of 6 times. Next, the stretched film was washed by immersing it in an aqueous solution (temperature 30°C) containing a potassium iodide concentration of 1.5% for 10 seconds. Next, the stretched film was dried at 50°C for 4 minutes, thereby obtaining a polarizer with a thickness of 30 μm. A transparent protective film (thickness 30 μm) formed of a modified acrylic polymer having a lactone ring structure was bonded to one main surface of the obtained polarizer using a polyvinyl alcohol adhesive. The TAC film with a hard coating layer (thickness 47 μm) was bonded to the other main surface of the polarizer of the TAC film with a hard coating layer (thickness 47 μm) using a polyvinyl alcohol adhesive. At this time, the other main surface of the polarizer was bonded to the transparent protective film. The bonding of the polarizer and the transparent protective film was performed using a roll laminator. After the polarizer and the transparent protective film were bonded, the obtained laminate was heated and dried at 70° C. for 5 minutes using an oven, thereby obtaining a laminate L1 consisting of a hard coating layer and a polarizing film.

[0227] [Conductive layer]

[0228] First, 50 parts of a solution containing PEDOT / PSS (Denatron PT-436 manufactured by Nagase ChemteX Corporation) and 50 parts of water were mixed to prepare a coating solution having a solid content concentration of 0.5% by weight. Next, the coating solution was applied to the surface of the polarizing film side of the laminate L1. The obtained coating film was dried at 80°C for 2 minutes to prepare a conductive layer. Thus, a laminate L2 consisting of a hard coat layer, a polarizing film, and a conductive layer was obtained. The thickness of the conductive layer was 30 nm.

[0229] [Adhesive layer]

[0230] First, a monomer mixture was obtained by adding 76.9 parts of butyl acrylate, 18 parts of benzyl acrylate, 5 parts of acrylic acid, and 0.1 parts of 4-hydroxybutyl acrylate to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser. Furthermore, 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator was added together with 100 parts of ethyl acetate to 100 parts of the monomer mixture (solid content). While slowly stirring the mixture, nitrogen was introduced into the flask to replace the nitrogen. The liquid temperature in the flask was maintained at about 55°C and a polymerization reaction was performed for 8 hours, thereby preparing a solution of an acrylic polymer with a weight average molecular weight (Mw) of 1.9 million and Mw / Mn=3.7.

[0231] Next, 0.45 parts of an isocyanate crosslinking agent (Coronate L manufactured by Tosoh Corporation, trimethylolpropane toluene diisocyanate), 0.1 parts of benzoyl peroxide (NYPER BMT manufactured by NOF Corporation) and 0.2 parts of γ-glycidoxypropylmethoxysilane (KBM-403 manufactured by Shin-Etsu Chemical Co., Ltd.) were further added to 100 parts of the solid content of the acrylic polymer solution to prepare a solution of an acrylic adhesive composition.

[0232] Next, the obtained solution was applied to one side of a separator (MRF38 manufactured by Mitsubishi Chemical Polyester Film Co., Ltd.). The separator was a polyethylene terephthalate film treated with a silicone release agent. The obtained coating film was dried at 155°C for 1 minute, thereby forming an adhesive layer on the surface of the separator. The thickness of the adhesive layer was 20 μm.

[0233] [Polarizing film with adhesive layer]

[0234] Next, the obtained pressure-sensitive adhesive layer was transferred onto the conductive layer of the laminate L2, thereby producing a pressure-sensitive adhesive layer-attached polarizing film of Example 1.

[0235] (Example 2)

[0236] A pressure-sensitive adhesive layer-attached polarizing film of Example 2 was prepared in the same manner as in Example 1, except that 1 part of lithium bis(trifluoromethanesulfonyl)imide manufactured by Mitsubishi Materials Corporation was further added as an ionic compound to the acrylic polymer solution to prepare a solution of an acrylic pressure-sensitive adhesive composition.

[0237] (Examples 3 and 4)

[0238] Pressure-sensitive adhesive layer-attached polarizing films of Examples 3 and 4 were produced in the same manner as in Example 1, except that the coating liquid of PEDOT / PSS was applied to the polarizing film so that the thickness of the conductive layer would be 20 nm and 90 nm, respectively.

[0239] (Example 5)

[0240] A laminate L2 including a hard coating layer, a polarizing film and a conductive layer was prepared by the following method. In addition, a polarizing film with an adhesive layer of Example 5 was prepared by the same method as Example 1. First, 9 parts of a solution containing PEDOT / PSS (Denatron P-580W manufactured by Nagase ChemteX Corporation) and 91 parts of water were mixed to prepare a coating liquid with a solid content concentration of 0.27% by weight. Next, the coating liquid was applied to the main surface of the polarizing film side of the above-mentioned laminate L1. The obtained coating film was dried at 80°C for 2 minutes to prepare a conductive layer. Thus, a laminate L2 consisting of a hard coating layer, a polarizing film and a conductive layer was obtained. The thickness of the conductive layer is 100nm.

[0241] (Example 6)

[0242] A polarizing film with an adhesive layer of Example 6 was prepared in the same manner as in Example 1, except that a polyurethane resin (SUPERFLEX 210 manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was further added as an adhesive to the coating solution for preparing the conductive layer. The content of the polyurethane resin in the conductive layer of Example 6 was 50% by weight.

[0243] (Example 7)

[0244] A polarizing film with an adhesive layer of Example 7 was produced in the same manner as in Example 2, except that a polyurethane resin (SUPERFLEX 210 manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was further added as an adhesive to the coating solution for producing the conductive layer. The content of the polyurethane resin in the conductive layer of Example 7 was 50% by weight.

[0245] (Example 8)

[0246] The coating liquid for making the conductive layer further contains a binder containing A polarizing film with an adhesive layer of Example 8 was prepared in the same manner as in Example 1 except that a solution of an oxazoline acrylic polymer (EPOCROS WS-700 manufactured by Nippon Shokubai Co., Ltd.) was added. The content of the oxazoline acrylic polymer was 50% by weight.

[0247] (Example 9)

[0248] The coating liquid for making the conductive layer further contains a binder containing A polarizing film with an adhesive layer of Example 9 was prepared in the same manner as in Example 2 except that a solution of an oxazoline acrylic polymer (EPOCROS WS-700 manufactured by Nippon Shokubai Co., Ltd.) was added. The content of the oxazoline acrylic polymer was 50% by weight.

[0249] (Example 10)

[0250] A pressure-sensitive adhesive layer-attached polarizing film of Example 10 was produced by the same method as in Example 1, except that the coating liquid of PEDOT / PSS was applied to the polarizing film so that the thickness of the conductive layer would be 5 nm.

[0251] (Example 11)

[0252] A pressure-sensitive adhesive layer-attached polarizing film of Example 11 was produced by the same method as in Example 2, except that the coating liquid of PEDOT / PSS was applied to the polarizing film so that the thickness of the conductive layer would be 5 nm.

[0253] (Example 12)

[0254] A pressure-sensitive adhesive layer-attached polarizing film of Example 12 was produced by the same method as in Example 1, except that the coating liquid of PEDOT / PSS was applied to the polarizing film so that the thickness of the conductive layer would be 150 nm.

[0255] (Comparative Example 1)

[0256] The thickness of the conductive layer becomes 15nm manner PEDOT / PSS coating solution is applied to the polarizing film, in addition, by the same method as in Example 5 prepared by the comparative example 1 with an adhesive layer of the polarizing film.

[0257] (Comparative Example 2)

[0258] A laminate L2 including a hard coating layer, a polarizing film and a conductive layer was prepared by the following method. In addition, a polarizing film with an adhesive layer of Comparative Example 2 was prepared by the same method as Example 1. First, 36.5 parts of a solution containing PEDOT / PSS (Denatron P-580W manufactured by Nagase ChemteX Corporation) and 63.5 parts of water were mixed to prepare a coating liquid with a solid content concentration of 1.1% by weight. Next, the coating liquid was applied to the main surface of the polarizing film side of the above-mentioned laminate L1. The obtained coating film was dried at 80°C for 2 minutes to prepare a conductive layer. Thus, a laminate L2 consisting of a hard coating layer, a polarizing film and a conductive layer was obtained. The thickness of the conductive layer is 350nm.

[0259] (Comparative Example 3)

[0260] A pressure-sensitive adhesive layer-attached polarizing film of Comparative Example 3 was produced by the same method as in Example 1 except that the conductive layer was not produced.

[0261] (Comparative Example 4)

[0262] A pressure-sensitive adhesive layer-attached polarizing film of Comparative Example 4 was produced by the same method as in Example 1, except that the coating liquid of PEDOT / PSS was applied to the polarizing film so that the thickness of the conductive layer would be 230 nm.

[0263] The following evaluations were performed on Examples 1 to 12 and Comparative Examples 1 to 4. The evaluation results are shown in Tables 1 and Figure 8 .

[0264] <Loss of total light transmittance A>

[0265] First, at the stage of making a laminate L1 composed of a hard coat layer and a polarizing film, the total light transmittance T3 of the laminate L1 was measured. The total light transmittance T3 was measured in accordance with the provisions of JIS K7361-1:1997 and using a spectrophotometer (V7100 manufactured by JASCO Corporation). The total light transmittance of the laminate L1 was measured by causing light to be incident from the hard coat side. By the same method, the total light transmittance T4 of the laminate L2 was measured at the stage of making a laminate L2 composed of a hard coat layer, a polarizing film and a conductive layer. The total light transmittance T4 of the laminate L2 was measured by causing light to be incident from the hard coat side. The difference between the total light transmittance T3 and the total light transmittance T4 (T3-T4) was calculated, and the calculated value obtained was regarded as the loss A of the total light transmittance caused by the conductive layer.

[0266] <Surface resistivity>

[0267] The surface resistivity of the conductive layer was measured using a laminate L2 consisting of a hard coat layer, a polarizing film, and a conductive layer. In Example 5, Comparative Example 1, and Comparative Example 2, the surface resistivity of the conductive layer was measured using a resistivity meter (Hiresta-UP MCP-HT450 manufactured by Mitsubishi Chemical Analytech Co., Ltd.) and in accordance with the method specified in JIS K6911:1995. The measurement conditions were an applied voltage of 10V and an application time of 10 seconds. In Examples 1 to 4, 6 to 12, and Comparative Example 4, the surface resistivity of the conductive layer was measured using a resistivity meter (Loresta-GP MCP-T600 manufactured by Mitsubishi Chemical Analytech Co., Ltd.) and in accordance with the method specified in JIS K7194:1994. The measurement conditions were an applied voltage of 10V and an application time of 10 seconds. In Examples 1 to 12 and Comparative Examples 1 to 4, the surface resistivity of the adhesive layer was measured using a resistivity meter (Hiresta-UP MCP-HT450 manufactured by Mitsubishi Chemical Analytech Co., Ltd.) at the stage of forming the adhesive layer on the separator. The measurement conditions were an applied voltage of 250 V and an application time of 10 seconds.

[0268] <ESD test>

[0269] The ESD test was performed on the polarizing film with an adhesive layer by the following method. First, the polarizing film with an adhesive layer was attached to the liquid crystal unit via the adhesive layer to produce a liquid crystal panel. Next, silver paste was applied with a width of 5 mm in a manner covering the sides of the polarizing film, conductive layer and adhesive layer of the liquid crystal panel. The silver paste was dried to form a conductive structure composed of silver. Through the conductive structure, the liquid crystal panel is electrically connected to the external ground electrode. Next, the liquid crystal panel was installed on the backlight device. Next, static electricity was applied to the visible side (polarizing film side) of the liquid crystal panel using an electrostatic discharge gun whose applied voltage was adjusted to 15kV. As a result, white spots appeared on a part of the liquid crystal panel. The time T from the time the static electricity was applied until the white spots disappeared was measured. In Table 1, the results of the ESD test were evaluated based on the following benchmarks related to time T. It should be noted that the ESD test was carried out under the conditions of 23°C and 55%RH.

[0270] (Evaluation Criteria)

[0271] A: Less than 0.5 seconds

[0272] B: More than 0.5 seconds and less than 1 second

[0273] C: More than 1 second and less than 10 seconds

[0274] D: More than 10 seconds

[0275] <Anchoring force>

[0276] The anchoring force between the conductive layer and the polarizing film was measured by the above method for the polarizing film with an adhesive layer. As a double-sided tape, the trade name "No.531" manufactured by Nitto Denko Corporation was used. As a stainless steel test plate, a SUS304 plate (40 mm wide × 120 mm long) was used. As an evaluation sheet, an ITO film (125Tetolight OES, manufactured by Oike Industries) was used. As a tensile testing machine, an Autograph SHIMAZU AG-I 10KN (manufactured by Shimadzu Corporation) was used.

[0277] [Table 1]

[0278]

[0279] (*1) Total light transmittance T3 of laminate L1 (%)

[0280] In the polarizing films with adhesive layers of Examples 1 to 12, the total light transmittance loss A caused by the conductive layer is 0.9% or less, so it is estimated that the deterioration of the visual recognition of the liquid crystal display device can be sufficiently suppressed. 6 The results of the ESD test of the polarizing films with pressure-sensitive adhesive layers of Examples 1 to 12 with a conductive layer having a thickness of Ω / □ or less were good, and it is inferred that the charging of the liquid crystal panel can be sufficiently suppressed. Figure 8 It is found that the total light transmittance loss A and the surface resistivity of the conductive layer are affected by the composition, thickness, etc. of the conductive layer.

[0281] <Examples and Comparative Examples Related to Polarizing Film with Pressure-Sensitive Adhesive Layer Having Antireflection Film>

[0282] [Adhesive layer A]

[0283] First, 76.9 parts of butyl acrylate, 18 parts of benzyl acrylate, 5 parts of acrylic acid, and 0.1 parts of 4-hydroxybutyl acrylate were added to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser to obtain a monomer mixture. Furthermore, 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator was added together with 100 parts of ethyl acetate relative to 100 parts of the monomer mixture (solid content). While slowly stirring the mixture, nitrogen was introduced into the flask to replace the nitrogen. The liquid temperature in the flask was maintained at about 55°C and a polymerization reaction was performed for 8 hours, thereby preparing a solution of an acrylic polymer with a weight average molecular weight (Mw) of 2 million and Mw / Mn=4.1.

[0284] Next, 0.45 parts of an isocyanate crosslinking agent (Coronate L manufactured by Tosoh Corporation, trimethylolpropane toluene diisocyanate), 0.1 parts of a peroxide crosslinking agent (NYPER BMT manufactured by NOF Corporation), and 0.2 parts of a silane coupling agent (KBM-403 manufactured by Shin-Etsu Chemical Co., Ltd., γ-glycidoxypropylmethoxysilane) were further added to 100 parts of the solid content of the acrylic polymer solution to prepare a solution of an acrylic adhesive composition.

[0285] Next, the obtained solution was applied to one side of a separator (MRF38 manufactured by Mitsubishi Chemical Polyester Film Co., Ltd.). The separator was a polyethylene terephthalate film treated with a silicone release agent. The obtained coating film was dried at 155° C. for 1 minute to form an adhesive layer A on the surface of the separator. The thickness of the adhesive layer A was 20 μm.

[0286] [Adhesive layer B]

[0287] Adhesive layer B was produced in the same manner as Adhesive layer A except that 1 part of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, manufactured by Mitsubishi Materials Corporation) was further added to 100 parts of the solid content of the acrylic polymer solution to prepare a solution of an acrylic adhesive composition.

[0288] [Adhesive layer C]

[0289] First, 94.9 parts of butyl acrylate, 5 parts of acrylic acid, and 0.1 parts of 4-hydroxybutyl acrylate were added to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser to obtain a monomer mixture. Furthermore, 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator was added together with 100 parts of ethyl acetate to 100 parts of the monomer mixture (solid content). While slowly stirring the mixture, nitrogen was introduced into the flask to replace the nitrogen. The liquid temperature in the flask was maintained at about 55°C and the polymerization reaction was carried out for 8 hours, thereby preparing a solution of an acrylic polymer with a weight average molecular weight (Mw) of 2.1 million and Mw / Mn=4.0.

[0290] Next, 0.45 parts of an isocyanate crosslinking agent (Coronate L manufactured by Tosoh Corporation, trimethylolpropane toluene diisocyanate), 0.1 parts of a peroxide crosslinking agent (NYPER BMT manufactured by NOF Corporation), and 0.2 parts of a silane coupling agent (KBM-403 manufactured by Shin-Etsu Chemical Co., Ltd., γ-glycidoxypropylmethoxysilane) were further added to 100 parts of the solid content of the acrylic polymer solution to prepare a solution of an acrylic adhesive composition.

[0291] Next, the obtained solution was applied to one side of a separator (MRF38 manufactured by Mitsubishi Chemical Polyester Film Co., Ltd.). The separator was a polyethylene terephthalate film treated with a silicone release agent. The obtained coating film was dried at 155° C. for 1 minute to form an adhesive layer C on the surface of the separator. The thickness of the adhesive layer C was 12 μm.

[0292] [Anti-reflective film AR1]

[0293] First, as resins for forming an anti-glare layer, 50 parts by weight of an ultraviolet-curable urethane acrylate resin (manufactured by Mitsubishi Chemical Corporation, trade name "UV1700TL", solid content concentration 80% by weight) and 50 parts by weight of a multifunctional acrylate containing pentaerythritol triacrylate as a main component (manufactured by Osaka Organic Chemical Industry Co., Ltd., trade name "Viscoat#300", solid content concentration 100% by weight) were prepared. For every 100 parts by weight of the solid content of these resins, 4 parts by weight of particles of a copolymer of (meth)acrylate and styrene (manufactured by Sekisui Chemicals Co., Ltd., trade name "Techpolymer SSX504TNR", weight average particle size: 3.0 μm), 1.5 parts by weight of an organic clay as a thixotropy imparting agent, i.e., synthetic montmorillonite (manufactured by Kunimine Industries Co., Ltd., trade name "Smekton SAN"), 3 parts by weight of a photopolymerization initiator (manufactured by BASF, trade name "OMNIRAD907"), and 0.015 parts by weight of a leveling agent (manufactured by DIC Corporation, trade name "GRANDIC PC4100", solid content concentration 10% by weight) were mixed. The mixture was diluted with a toluene / cyclopentanone mixed solvent (weight ratio 80 / 20) so that the solid content concentration became 50% by weight, thereby preparing a material (coating liquid) for forming an anti-glare layer.

[0294] Next, a triacetylcellulose (TAC) film (manufactured by Fuji Film Co., Ltd., trade name "TD60UL") was prepared. A material (coating liquid) for forming an anti-glare layer was applied to one side of the transparent plastic film (TAC film) using a wire bar coater to form a coating film. Next, the transparent plastic film with the coating film was heated at 80°C for 1 minute to dry the coating film. Next, the coating film was irradiated with a high-pressure mercury lamp with a cumulative light intensity of 300 mJ / cm 2 The TAC film with an antiglare layer having an antiglare layer thickness of 8.0 μm was obtained. The haze of the TAC film with an antiglare layer was 8%.

[0295] Next, the TAC film with the anti-glare layer was introduced into a roll-to-roll sputtering film forming device and the film was allowed to travel, thereby bombarding the surface of the anti-glare layer (using Ar gas plasma treatment). Next, a SiO2 film with a physical film thickness of 3 nm was formed on the surface of the anti-glare layer as a bonding layer. x Layer (x<2). Next, a Nb2O5 layer (first high refractive index layer) with a physical film thickness of 12nm, a SiO2 layer (first low refractive index layer) with a physical film thickness of 29nm, a Nb2O5 layer (second high refractive index layer) with a physical film thickness of 116nm, and a SiO2 layer (second low refractive index layer) with a physical film thickness of 78nm were sequentially formed on the adhesion layer to produce a laminate a. When forming these oxide thin films, the pressure in the device was kept constant by adjusting the introduction and exhaust volume of argon gas, and the amount of oxygen introduced was adjusted by plasma glow emission monitoring (PEM) control.

[0296] Next, a layer (physical film thickness: 9 nm) made of a fluorine-based resin as an antifouling layer was formed on the surface of the second low refractive index layer (SiO2 layer) of the laminate a. The adhesive layer C was further transferred to the surface of the TAC film of the laminate a to prepare an antireflection film AR1.

[0297] [Anti-reflection film AR2~AR10]

[0298] Except that the physical film thickness of each layer was changed to the value shown in Table 2, the antireflection films AR2 to AR10 were produced by the same method as the antireflection film AR1.

[0299] [Table 2]

[0300]

[0301] [Polarizing film P1]

[0302] First, an acrylic film was prepared by the following method. 8000 g of methyl methacrylate (MMA), 2000 g of methyl 2-(hydroxymethyl)acrylate (MHMA), 10000 g of 4-methyl-2-pentanone (methyl isobutyl ketone, MIBK), and 5 g of n-dodecyl mercaptan were added to a 30 L kettle reactor equipped with a stirring device, a temperature sensor, a condenser, and a nitrogen inlet pipe. While introducing nitrogen into the reactor, the mixture in the reactor was heated to 105°C and refluxed. Next, 5.0 g of tert-butyl peroxyisopropyl carbonate (Kayakarubon BIC-7, manufactured by KayakuAkzo Co., Ltd.) was added as a polymerization initiator, and a solution made of 10.0 g of tert-butyl peroxyisopropyl carbonate and 230 g of MIBK was dripped over 4 hours to perform solution polymerization. Solution polymerization was performed at about 105 to 120°C under reflux. After the solution was dripped, it was further aged for 4 hours.

[0303] Next, 30 g of a mixture of stearyl phosphate / distearyl phosphate (Phoslex A-18, manufactured by Sakai Chemical Industry) was added to the obtained polymer solution, and a cyclocondensation reaction was carried out at about 90 to 120° C. for 5 hours under reflux. Next, the obtained solution was introduced into a vented twin-screw extruder (φ=29.75 mm, L / D=30) with a barrel temperature of 260° C., a rotation speed of 100 rpm, a reduced pressure of 13.3 to 400 hPa (10 to 300 mmHg), 1 rear vent hole, and 4 front vent holes at a processing rate of 2.0 kg / h according to the resin amount. Further cyclocondensation reaction and devolatilization were carried out in the extruder. Thus, transparent particles of a lactone ring-containing polymer were obtained.

[0304] The obtained lactone ring-containing polymer was subjected to dynamic TG measurement, and a mass loss of 0.17 mass % was detected. The lactone ring-containing polymer had a weight average molecular weight of 133,000, a melt flow rate of 6.5 g / 10 min, and a glass transition temperature of 131°C.

[0305] The obtained pellets were kneaded and extruded with acrylonitrile-styrene (AS) resin (ToyoAS AS20, manufactured by Toyo Styrene Co., Ltd.) at a mass ratio of 90 / 10 using a single screw extruder (screw 30 mmφ) to obtain transparent pellets. The obtained pellets had a glass transition temperature of 127°C.

[0306] The pellets were melt-extruded from a 400 mm wide coat hanger T die using a 50 mm φ single screw extruder to produce a 120 μm thick film. The film was stretched to 2.0 times in the longitudinal direction and 2.0 times in the transverse direction at a temperature of 150° C. using a biaxial stretching device to obtain a 30 μm thick stretched film (acrylic film). The optical properties of the stretched film were measured, and the results showed that the total light transmittance was 93%, the in-plane phase difference Δnd was 0.8 nm, and the thickness direction phase difference Rth was 1.5 nm.

[0307] Next, a polarizing film P1 was produced by the following method. First, a polyvinyl alcohol film with a thickness of 45 μm was dyed in a 0.3% iodine solution (temperature 30°C) between multiple rollers with different speed ratios for 1 minute, and stretched to a stretch ratio of 3 times. Next, the obtained stretched film was immersed in an aqueous solution (temperature 60°C) containing 4% boric acid and 10% potassium iodide for 0.5 minutes, and stretched to a total stretch ratio of 6 times. Next, the stretched film was immersed in an aqueous solution (temperature 30°C) containing 1.5% potassium iodide for 10 seconds and washed. Next, a polarizer with a thickness of 18 μm was obtained by drying the stretched film at 50°C for 4 minutes. A TAC film with a thickness of 40 μm (manufactured by Konica Minolta, trade name "KC4UY") was bonded to one main surface of the obtained polarizer using a polyvinyl alcohol adhesive. The aforementioned acrylic film having a thickness of 30 μm was bonded to the other main surface of the polarizer with a polyvinyl alcohol-based adhesive. Thus, a polarizing film P1 was obtained.

[0308] (Example 13)

[0309] First, 50 parts of a solution containing PEDOT / PSS (Denatron PT-436 manufactured by Nagase ChemteX Corporation) and 50 parts of water were mixed to prepare a coating solution having a solid content concentration of 0.5% by weight. Next, the coating solution was applied to the surface of the acrylic film side of the polarizing film P1. The obtained coating film was dried at 80°C for 2 minutes to prepare a conductive layer. Thus, a polarizing film with a conductive layer was obtained. The thickness of the conductive layer was 30 nm.

[0310] Next, the adhesive layer C of the antireflection film AR1 was bonded to the surface of the TAC film of the polarizing film P1. The adhesive layer A was further transferred to the surface of the conductive layer to prepare a polarizing film with an adhesive layer of Example 13 having a structure of antireflection film AR1 / polarizing film P1 / conductive layer / adhesive layer A.

[0311] (Example 14)

[0312] A pressure-sensitive adhesive layer-attached polarizing film of Example 14 was produced by the same method as in Example 13, except that the coating liquid of PEDOT / PSS was applied to the polarizing film P1 so that the thickness of the conductive layer would be 90 nm.

[0313] (Examples 15 to 24, 26 and Comparative Example 5)

[0314] Polarizing films with adhesive layers of Examples 15 to 24, 26 and Comparative Example 5 were prepared by the same method as Example 13, except that the antireflection film, the conductive layer and the adhesive layer were changed to the combinations shown in Table 3. It should be noted that in Comparative Example 5, the conductive layer was not formed on the polarizing film P1, and the adhesive layer A was directly bonded to the surface of the polarizing film P1 on the acrylic film side.

[0315] (Example 25)

[0316] First, a coating solution having a solid content concentration of 0.27% by weight was prepared by mixing 9 parts of a solution containing PEDOT / PSS (Denatron P-580W manufactured by Nagase ChemteX Corporation) and 91 parts of water. Next, the coating solution was applied to the surface of the acrylic film side of the polarizing film P1. A conductive layer was prepared by drying the obtained coating film at 80°C for 2 minutes. Thus, a polarizing film with a conductive layer was obtained. The thickness of the conductive layer was 100 nm.

[0317] Next, the adhesive layer C of the antireflection film AR4 was bonded to the surface of the TAC film of the polarizing film P1. The adhesive layer A was further transferred to the surface of the conductive layer to prepare a polarizing film with an adhesive layer of Example 25 having a structure of antireflection film AR4 / polarizing film P1 / conductive layer / adhesive layer A.

[0318] (Comparative Example 6)

[0319] First, 8.6 parts of a solution containing PEDOT / PSS (Denatron P-580W manufactured by Nagase ChemteX Corporation) and A coating liquid (solid content concentration of 0.5 wt %) for forming a conductive layer was prepared by mixing 1 part of a solution of an oxazoline acrylic polymer (trade name: EPOCROS WS-700, manufactured by Nippon Shokubai) and 90.4 parts of water. The concentration of the polythiophene polymer in the obtained coating liquid was 0.04 wt %, and the content of The concentration of the oxazoline acrylic polymer was 0.25% by weight.

[0320] Next, the obtained coating liquid was applied to the main surface of the polarizing film P1 on the acrylic film side. The obtained coating film was dried at 80° C. for 2 minutes to prepare a conductive layer. Thus, a polarizing film with a conductive layer was obtained. The thickness of the conductive layer was 60 nm.

[0321] Next, the adhesive layer C of the antireflection film AR10 was bonded to the surface of the TAC film of the polarizing film P1. The adhesive layer A was further transferred to the surface of the conductive layer to prepare a polarizing film with an adhesive layer of Comparative Example 6 having a structure of antireflection film AR10 / polarizing film P1 / conductive layer / adhesive layer A.

[0322] <Optical properties of the polarizing film with pressure-sensitive adhesive layer>

[0323] For the polarizing films with adhesive layers obtained in Examples 13 to 26 and Comparative Examples 5 to 6, when the adhesive layer was laminated on the alkali-free glass in a manner that the adhesive layer was directly in contact with the alkali-free glass, light from a CIE standard light source D65 was incident from the antireflection film, and the light reflectance ratios Y and L of the reflected light generated at this time were measured by the above-mentioned method. * Value, a * Value and b * value, and satisfy L * Value = 0, a * Value = 0 and b * The color difference ΔE between the light with a value = 0 and the reflected light was evaluated. At this time, the polarizing film with an adhesive layer was cut into 50 mm squares for use. As the alkali-free glass, EG-XG (thickness 0.7 mm) manufactured by Corning Incorporated was used. As the black film, a black film made of polyethylene terephthalate (PET) was used. The spectral reflectance was measured using a spectrophotometer (manufactured by Konica Minolta, Ltd., trade name "CM2600D"). The evaluation sample for evaluating the optical properties has a structure of a polarizing film with an adhesive layer / alkali-free glass / black PET film. Among them, for the polarizing film with an adhesive layer of Example 26, the reflected light was evaluated using an alkali-free glass on which an amorphous ITO layer (thickness 20 nm) was not formed on the surface. That is, in Example 26, the evaluation sample has a structure of a polarizing film with an adhesive layer / ITO layer / alkali-free glass / black PET film. Sputtering was used to make the ITO layer. The Sn ratio of ITO contained in the ITO layer is 3 weight%. The Sn ratio was calculated from the weight of Sn atoms in ITO / (weight of Sn atoms+weight of In atoms).

[0324] <Optical properties of anti-reflection films>

[0325] For the antireflection films AR1 to AR10, the light reflectances Y1 and a1 of the reflected light generated when light from the CIE standard light source D65 is incident by the above method are * Value and b1* The same black film, spectrophotometer, and the like as those used in the evaluation of the optical properties of the pressure-sensitive adhesive layer-attached polarizing film were used.

[0326] <Surface resistivity of adhesive layer>

[0327] The surface resistivity (Ω / □) of the adhesive layer A and B was measured at the stage of forming the adhesive layer A or B on the surface of the separator. The surface resistivity was measured using a resistivity meter (Hiresta-UP MCP-HT450 manufactured by Mitsubishi Chemical Analytech Co., Ltd.). The measurement conditions were an applied voltage of 250 V and an applied time of 10 seconds.

[0328] <Surface resistivity of conductive layer>

[0329] In Examples 13 to 26 and Comparative Example 6, the surface resistivity (Ω / □) of the conductive layer was measured at the stage of forming the conductive layer on the surface of the polarizing film P1. In Example 25 and Comparative Example 6, the surface resistivity of the conductive layer was measured using a resistivity meter (Hiresta-UP MCP-HT450 manufactured by Mitsubishi Chemical Analytech Co., Ltd.) and in accordance with the method specified in JIS K6911:1995. The measurement conditions were an applied voltage of 10 V and an application time of 10 seconds. In Examples 13 to 24 and 26, the surface resistivity of the conductive layer was measured using a resistivity meter (Loresta-GP MCP-T600 manufactured by Mitsubishi Chemical Analytech Co., Ltd.) and in accordance with the method specified in JIS K7194:1994. The measurement conditions were an applied voltage of 10 V and an application time of 10 seconds.

[0330] <Surface resistivity of polarizing film>

[0331] In Comparative Example 5, the surface resistivity of the polarizing film P1 was measured using a resistivity meter (Hiresta-UP MCP-HT450 manufactured by Mitsubishi Chemical Analytech Co., Ltd.) in accordance with the method specified in JIS K6911:1995. The measurement conditions were an applied voltage of 10 V and an applied time of 10 seconds. The surface resistivity of the polarizing film P1 was higher than 1.0×10 14 Ω / □.

[0332] <Loss of total light transmittance A caused by conductive layer>

[0333] First, the total light transmittance T1 of the polarizing film P1 was measured using a spectrophotometer (V7100 manufactured by JASCO Corporation) in accordance with the provisions of JIS K7361-1:1997. In the same way, the total light transmittance T2 of the laminate L composed of the polarizing film P1 and the conductive layer was measured at the stage where the conductive layer was formed on the surface of the polarizing film P1. The total light transmittance T2 of the laminate L was measured by allowing light to enter from the side of the polarizing film P1. The difference (T1-T2) between the total light transmittance T1 and the total light transmittance T2 of the polarizing film P1 was calculated, and the calculated value was regarded as the loss A of the total light transmittance caused by the conductive layer.

[0334] <ESD test>

[0335] First, the polarizing film with an adhesive layer obtained in Examples 13 to 26 and Comparative Examples 5 to 6 was bonded to the surface of the visible side of the liquid crystal unit to produce a liquid crystal panel. Among them, for Example 26, a liquid crystal unit with an amorphous ITO layer (thickness 20nm) formed on the surface was used. That is, in Example 26, the liquid crystal panel has a structure of a polarizing film with an adhesive layer / ITO layer / liquid crystal unit. Sputtering was used to make the ITO layer. The Sn ratio of the ITO contained in the ITO layer is 3% by weight. Next, silver paste was applied with a width of 5mm in a manner covering the side of the polarizing film with an adhesive layer. The silver paste was dried to form a conductive structure composed of silver. The liquid crystal panel is electrically connected to the external ground electrode through the conductive structure. Next, the liquid crystal panel was installed on the backlight device. Next, an electrostatic discharge (ESD) gun with an applied voltage adjusted to 10kV was used to apply static electricity to the visible side (anti-reflection film side) of the liquid crystal panel. As a result, white spots appeared on a portion of the liquid crystal panel. The time T from the time the static electricity was applied until the white spots disappeared was measured. In Table 3, the results of the ESD test were evaluated based on the following criteria related to the time T. In addition, the ESD test was performed under the conditions of 23° C. and 55% RH.

[0336] (Evaluation Criteria)

[0337] A: Less than 0.5 seconds

[0338] B: More than 0.5 seconds and less than 1 second

[0339] C: More than 1 second and less than 10 seconds

[0340] D: More than 10 seconds

[0341] <Color tone>

[0342] The liquid crystal panel produced in the above-mentioned ESD test was observed by naked eyes from the visible side (anti-reflection film side) to evaluate the color tone. In the color tone items in Table 3, A means no color tone is confirmed, B means very weak color tone is confirmed, C means weak color tone is confirmed, and D means color tone is confirmed.

[0343]

[0344] According to Table 3, for the polarizing films with adhesive layers of Examples 13 to 26, the total light transmittance loss A caused by the conductive layer is 0.9% or less, so it is inferred that the deterioration of the visual recognition of the liquid crystal display device can be fully suppressed. 6 The results of the ESD test of the polarizing film with an adhesive layer of Examples 13 to 26 with a conductive layer of less than Ω / □ are good, and it is inferred that the charging of the liquid crystal panel can be fully suppressed. According to the results of the ESD test of Examples 15 and 26, by using an adhesive layer with a conductive material added together with the conductive layer, the charging of the liquid crystal panel can be fully suppressed compared to the case of using an ITO layer. In addition, according to the results of Examples 24 and 26, when an ITO layer is not configured between the polarizing film with an adhesive layer and the liquid crystal unit, the value of the light reflectance ratio Y of the reflected light is low, and the reflection of light is fully suppressed.

[0345] In addition, for those who have the ability to generate a * Value and b * For the liquid crystal panels with polarizing films with adhesive layers of Examples 13 to 23 and Examples 25 to 26, whose values ​​satisfy the relational expressions (1) and (2), the hue cannot be confirmed, or even if it can be confirmed, it is to a degree that does not cause problems in practical use, compared with the liquid crystal panels with polarizing films with adhesive layers of Example 24 and Comparative Examples 5 and 6. That is, the reflected light from the liquid crystal panels with polarizing films with adhesive layers of Examples 13 to 23 and Examples 25 to 26 has a natural hue.

[0346] Industrial Applicability

[0347] The pressure-sensitive adhesive layer-attached polarizing film of the present invention can be suitably used in a liquid crystal display device used in an environment where static electricity is likely to be generated, particularly in an environment where other electronic devices are present around such as the interior of a vehicle.

Claims

1. A polarizing film with an adhesive layer, comprising a polarizing film and an adhesive layer, The polarizing film with an adhesive layer further comprises a conductive layer. The polarizing film with an adhesive layer satisfies at least one of the following (i) and (ii): (i) The total light transmittance loss caused by the conductive layer is less than 0.5%, and the surface resistivity of the conductive layer is 1.0×10 6 Ω / □ or less, (ii) the total light transmittance loss caused by the conductive layer is greater than 0.5% and less than 0.9%, and the surface resistivity of the conductive layer is 1.0×10 4 Ω / □ or less, The above (i) and (ii) are achieved by adjusting the composition of the conductive material in the conductive layer, the content of the conductive material, and the thickness of the conductive layer.

2. The polarizing film with an adhesive layer according to claim 1, wherein The polarizing film, the conductive layer, and the adhesive layer are stacked together in the above order.

3. The polarizing film with an adhesive layer according to claim 1, wherein When the above condition (i) is satisfied, the loss is 0.4% or less.

4. The polarizing film with an adhesive layer according to claim 1, wherein When the above (i) is satisfied, the surface resistivity is 5.0×10 5 Ω / □ or less.

5. The polarizing film with an adhesive layer according to claim 1, wherein When the above (i) is satisfied, the surface resistivity is 1.0×10 4 Ω / □ or less.

6. The polarizing film with an adhesive layer according to claim 1, wherein The surface resistivity is greater than 5.0×10 2 Ω / □.

7. The polarizing film with an adhesive layer according to claim 1, wherein The adhesive layer includes a conductive material.

8. The polarizing film with an adhesive layer according to claim 1, further comprising an antireflection film. The antireflection film, the polarizing film, and the adhesive layer are arranged in the above order in a lamination direction.

9. The polarizing film with an adhesive layer according to claim 8, wherein When the adhesive layer is laminated on the alkali-free glass in direct contact with the alkali-free glass, when light from CIE standard light source D65 is incident from the surface opposite to the adhesive layer, reflected light having a light reflectance Y of 1.1% or less is generated.

10. The polarizing film with an adhesive layer according to claim 9, wherein The reflected light is L * a * b * a in the color system * Value and b * The values ​​satisfy the following relations (1) and (2), -10≤a * ≤10 (1) -18≤b * ≤5 (2)。 11. The polarizing film with an adhesive layer according to claim 8, wherein The antireflection film includes a first high refractive index layer, a first low refractive index layer, a second high refractive index layer, and a second low refractive index layer in this order in a lamination direction.

12. The polarizing film with an adhesive layer according to claim 11, wherein The optical film thickness of the first high refractive index layer is 20 nm to 35 nm. The optical film thickness of the first low refractive index layer is 38 nm to 50 nm. The optical film thickness of the second high refractive index layer is 230nm to 290nm. The optical film thickness of the second low refractive index layer is 100 nm to 128 nm.

13. A liquid crystal panel comprising: The polarizing film with an adhesive layer according to any one of claims 1 to 12, and Liquid crystal unit, No conductive layer is provided between the pressure-sensitive adhesive layer-attached polarizing film and the liquid crystal cell.

Citation Information

Patent Citations

  • Conductive polymer layer as an antistatic protective shield for polarizing filters

    JP2015509615A

  • Transparent conductor, liquid crystal display device, and method for manufacturing transparent conductor

    JP2016039132A

  • Composition for static dissipative coating layer, polarizing plate and optical display apparatus

    CN108219659A

  • Anti-reflective film having high surface hardness and antistatic property and method for producing the same

    WO2007004818A1

  • In-cell liquid crystal panel and liquid crystal display device

    WO2018181477A1